Responses of Liolaemus lizards to environmental heterogeneity: Linking microhabitat selection and thermal ecology in southern Patagonia - Candela Victorel; Mauro I. Bonavita; Martin C. Castillo; Débora L. Moreno Azocar; María G. Perotti; Félix B. Cruz; Oscar A. Stellatelli (Journal of Thermal Biology, 2026)

De novo Genome Assembly, Annotation, and Comparative Analysis of the Lined Sole Achirus lineatus as a Resource for Evolutionary and Environmental Genomics - Mercedes Quintanilla-Mena; Elsa B. Góngora-Castillo; Rossanna Rodriguez-Canul; Rafael Rivera-Bustamante (Marine Biotechnology, 2026)
The lined sole, Achirus lineatus , is a widely distributed species in the Gulf of Mexico. This basin is constantly exposed to hydrocarbon contamination due to natural oil seeps, oil extraction and oil spills. Previous studies suggest the line sole A. lineatus as a possible sentinel species for oil spills; but the overall landscape of xenobiotic metabolism in this species remains poorly understood. Access to high-quality reference genomes will improve this situation. Here, we report the first whole-genome sequence, assembly, and annotation of the lined sole A. lineatus . We generated 132 Gb of PacBio High-Fidelity (HiFi) reads, which were filtered to retain 93 Gb of ultra-high-quality data. The assembly resulted in a mitogenome of 16,579 bp and a nuclear genome of 486.3 Mb distributed across 199 contigs, with a contig N50 of 9.87 Mb. Benchmarking Universal Single-Copy Orthologs (BUSCO) analysis based on the actinopterygii _odb10 database (3,640 orthologs) identified 3,611 (99.2%) complete BUSCOs. Genome annotation strategy resulted in the identification of 22,412 protein-coding genes with a high percentage (95.94%) of functional annotation. The genome of A. lineatus revealed 693 expanded and 3349 contracted gene families. We also identified 123 genes involved in the xenobiotics biodegradation and metabolism pathways, as well as neuroplasticity-related genes that may be associated with responses to environmental toxicants, providing baseline genomic information that suggests an integrated adaptive strategy involving both metabolic and nervous system processes. This assembly represents a valuable genomic resource for future toxicological and ecological studies of this species.

Continent-wide stock structure and connectivity of silver trevally (Pseudocaranx georgianus) based on population genomics and otolith shape and chemistry - Zoriana H.T. Lam; John Stewart; Jonathan Sandoval-Castillo; Patrick Reis-Santos; Rhiannon A. Van Eck; Bronwyn M. Gillanders; Peter Ritchie; Maren Wellenreuther; Charlie Huveneers; David V. Fairclough; Ashley M. Fowler; Julian Hughes; et al. (Fisheries Research, 2026)

Cultural Importance of Asteraceae for Beekeeping and Traditional Medicine in the Yucatan Peninsula Region, Mexico - Justo R. Enríquez-Nolasco; William Cetzal-Ix; Iván Tamayo-Cen; Saikat Kumar Basu; Fernando Casanova-Lugo; Benito B. Dzib-Castillo (The Botanical Review, 2026)

Prediction of Adverse effects of Geomagnetic storms and Energetic Radiation (PAGER) project - Yuri Y. Shprits; Tony Arber; Michael Liemohn; Ondřej Santolík; Keith Bennett; Stefano Bianco; Melanie Burns; Angelica Castillo; Marina García Peñaranda; Bernhard Haas; Julia Himmelsbach; Artem Smirnov; et al. (Advances in Space Research, 2026)

Environmental Gradients Decouple Demographic and Adaptive Connectivity in a Highly Mobile Coastal Marine Species - Chris J. Brauer; Andrea Bertram; Jonathan Sandoval‐Castillo; Anthony Fowler; Justin D. Bell; Paul Hamer; Maren Wellenreuther; Luciano B. Beheregaray (Molecular Ecology, 2026)
Understanding how eco‐evolutionary processes shape genetic variation and persistence in marine species with highly variable recruitment dynamics and dispersal potential remains a fundamental challenge, particularly when considering the interplay between gene flow and local adaptation. Here, we employed a seascape genomics approach to investigate population connectivity and local adaptation in Australasian snapper ( Chrysophrys auratus , Sparidae) along 1500 km of the environmentally heterogeneous southern Australian coastline. Using genome‐wide SNPs, we identified distinct eastern and western regional populations aligned with known biogeographical regions. Genotype‐environment association analyses revealed 855 candidate adaptive loci associated with environmental variation, including temperature, salinity and primary productivity. Connectivity analyses using neutral markers indicated high gene flow within both eastern and western regions, while candidate adaptive loci revealed substantially reduced connectivity, especially for Northern Spencer Gulf and West Coast populations. This contrast implies a decoupling of demographic and adaptive connectivity, in which strong environmental gradients appear to reduce the effective exchange of adaptive variation despite high overall connectivity. Our results support contingent migration as a potential mechanism modulating the balance between local adaptation and gene flow in this economically and ecologically important marine species. These findings might also have implications for regional management of other coastal fisheries that are experiencing substantial declines. As climate change alters coastal marine environments around the world, the dynamics of local recruitment, site fidelity and local adaptation are expected to change. This highlights the importance of integrating knowledge about eco‐evolutionary processes into marine resource management, fisheries stock assessment, and restocking and stock enhancement activities.

Dynamics of coastal picoeukaryote communities in response to oil spill disturbances - B. Glasner; I. Morel-Letelier; E. Osses; C. Galvez-Aracena; P. Ávila-Guerrero; C. Henríquez-Castillo; E. Urrejola-Pulido; C.B. Pareja; A.A. Durán; N. Trefault; R. De la Iglesia (Marine Environmental Research, 2026)

Simultaneous consumption of Liolaemus lizards by the raptor Geranoaetus polyosoma in south-central patagonia - Candela Victorel; Martín C. Castillo; Mauro I. Bonavita; Mauro N. Tammone; Laura M. Casalins; Laura Mangini Mas; Valeria S. Ojeda; Débora L. Moreno Azócar; Marcelo F. Bonino; Félix B. Cruz (acta ethologica, 2026)

Fermentation of rice milling by-products can completely replace soybean meal in the diet of Oreochromis niloticus fingerlings - Mark Henry F. De Leon; Dinah Grace D. Bienes; Mary Jessa Bell B. Pagapulan; Emelyn Joy G. Mameloco; Vyenge Erre D. Gayosa; Fredson H. Huervana; Carmelo S. del Castillo; Rex Ferdinand M. Traifalgar (Frontiers in Marine Science, 2026)
The expansion and intensification of aquaculture have been widely adopted to support large-scale production, creating a reliance on high-protein feed ingredients such as soybean meal (SBM) and fish meal (FM). These ingredients, however, are costly and unsustainable, emphasizing the need for alternative plant-based protein sources for aquafeeds. This study assessed the nutritional and feed value of fermented rice bran meal (FRBM) as a substitute for SBM in the diet of tilapia ( Oreochromis niloticus ) fingerlings. Five diets were formulated with FRBM replacing SBM at 0%, 25%, 50%, 75%, and 100%, and were fed to fingerlings over a 60-day period. Results showed that FRBM could fully replace SBM, with growth-promoting effects particularly observed at 25% replacement. Survival, percentage weight gain, feed conversion ratio (FCR), and specific growth rate (SGR) did not differ significantly among the treatments with varying FRBM levels. No significant differences in carcass composition (protein, lipid, and ash) were observed among tilapia fed with diets containing FRBM replacement. The apparent protein and dry matter digestibility coefficients of FRBM are 91.52% and 66.67%, respectively. Histological examination also revealed no intestinal abnormalities, even at the highest level of FRBM inclusion. Overall, the findings suggest that solid-state fermented rice bran can fully replace soybean meal in the diet of O. niloticus . In addition, its use presents a practical option to help meet the growing protein requirements in aquafeeds and to promote the sustainable expansion of tilapia aquaculture.

Functional characterization of splice variants in hereditary breast and ovarian cancer susceptibility genes - Laura Rosado-Jiménez; Younes Mestre-Terkemani; Ángeles García-Aliaga; María D. Sarabia-Meseguer; Miguel Marín-Vera; José A. Macías-Cerrolaza; Pilar Sánchez-Henarejos; María R. García-Hernández; Marta Zafra-Poves; Beatriz C. Álvarez-Abril; Carmen B. López-Sánchez; María P. Moya-Martínez; et al. (Familial Cancer, 2025)

Bridging yield gaps in rice production through integrated crop and nutrient management with farmer groups - Hasil Sembiring; Setia Sari Girsang; Arif Anshori; Erythrina Erythrina; Pepi Nur Susilawati; Andy Bhermana; Yohanis Ngongo; Sidiq Hanapi; Darojat Prawiranegara; Nuning A. Subekti; Priatna Sasmita; Irish Lorraine B. Pabuayon; et al. (Field Crops Research, 2025)

Adaptive responses to thinning: Growth and sensitivity to hydric and thermal stress in four widely planted pine species - Àngela Manrique-Alba; Santiago Beguería; J. Julio Camarero; Antonio J. Molina; Gonzalo G. Barberá; Juan A. Blanco; Antonio M. Cachinero-Vivar; Víctor M. Castillo; Antonio D. del Campo; Álvaro Hernández; J. Bosco Imbert; María N. Jiménez; et al. (Agricultural and Forest Meteorology, 2025)

Conservation Arks: Genomic Erosion and Inbreeding in an Abundant Island Population of Koalas - Katie Gates; Jonathan Sandoval‐Castillo; Julian E. Beaman; Karen Burke da Silva; Frédérik Saltré; Katherine Belov; Carolyn J. Hogg; Corey J. A. Bradshaw; Luciano B. Beheregaray (Molecular Ecology, 2025)
The persistence of many threatened species depends on isolated habitat patches such as conservation parks, fenced reserves, and islands. While these ‘conservation arks’ provide refuge from many contemporary threats, they can also pose risks of genetic diversity loss and inbreeding depression, further exacerbating extinction risk. A pertinent example is the Kangaroo Island koala population in South Australia that originated from a few translocated founding individuals in the 1920s but now sustains a large population with a low prevalence of infectious disease. We investigated the extent and consequences of founder effects on genomic diversity, inbreeding, and adaptive potential in Kangaroo Island koalas by comparing them with mainland Australian populations using high‐coverage whole genomes. Our findings support sharp, recent declines in effective population sizes ( N e ) in both mainland and Kangaroo Island populations. However, Kangaroo Island koalas had much lower individual and population‐level diversity. Together with longer and more numerous runs of homozygosity and an increased proportion of homozygous genetic load, these results support the hypothesis that a severe bottleneck has contributed to inbreeding and maladaptation in Kangaroo Island koalas. While Kangaroo Island has the potential to conserve a viable population of koalas, we recommend genetic rescue to restore diversity and mitigate inbreeding depression in this isolated population. Our results emphasise the need for longitudinal genomic monitoring and genetic management to maintain long‐term viability and resilience in potential conservation arks. Understanding the demographic history of such populations will help inform future conservation aimed at preventing genetic erosion and preserving biodiversity.

Cadmium removal and indole acetic acid production by ureolytic bacteria isolated from rhizosphere soils - Carlos A. Adarme-Duran; Elianna Castillo; Pedro F. B. Brandão (World Journal of Microbiology and Biotechnology, 2025)
This work reports the isolation of 54 ureolytic bacteria with microbiologically induced carbonate precipitation (MICP) activity from Theobroma cacao L. rhizosphere soils with Cd concentration ranging from 0.49 to 21.29 mg kg − 1 . Analysis of the 16 S rRNA gene showed the isolates belong to the genera Serratia , Pseudomonas , Comamonas , Klebsiella , Bacillus , Citrobacter , Flavobacterium , Delftia , and Stenotrophomonas . They showed ureolytic activity between 0.31 and 1.01 µmol NH 4 + mL − 1 h − 1 and produced the phytohormone indole acetic acid (IAA). Interestingly, Cd was observed to increase ureolytic activity and did not affect the IAA production of various isolates. Cadmium removal in solution ranged from 4.4 to 87.0% after 48 h. Strains Serratia sp. 89a, Klebsiella sp. 76 h, and Stenotrophomonas sp. 67w exhibited the best performance (> 80%). Cadmium removal through MICP by the genera Delftia , Flavobacterium , and Klebsiella is reported for the first time. Results suggest the isolated bacteria have the potential for Cd bioremediation and could be used to alleviate metal-induced stress through IAA production.

Productivity and nutritional quality of pastures in a silvopastoral system under two harvest intervals in southeastern Mexico - Benito B. Dzib-Castillo; Fernando Casanova-Lugo; Dixan Pozo-Leyva; Ricardo L. D. Costa; Laura Macario-González; Flavia M. A. Gimenes; Luis A. Lara-Pérez; Alfonso J. Chay-Canul (Agroforestry Systems, 2025)

Site-specific nutrient management for rice using soil properties to adjust phosphorus and potassium supply from compound NPK fertilizer - Setia Sari Girsang; Rowena L. Castillo; Mahyuddin Syam; Zulkifli Zaini; Sunendar Kartaatmadja; Suyamto; Judith Carla Dela Torre; Irish Lorraine B. Pabuayon; Romalene A. Limpiada; Waluyo; Helmi; Samijan; et al. (Field Crops Research, 2025)

Safety Outcomes of Antiplatelet Therapy During Endovascular Treatment of Tandem Lesions in Acute Ischemic Stroke Patients - Mudassir Farooqui; Afshin A. Divani; Milagros Galecio-Castillo; Ameer E. Hassan; Mouhammad A. Jumaa; Marc Ribo; Michael Abraham; Nils Petersen; Johanna Fifi; Waldo R. Guerrero; Amer M. Malik; James E. Siegler; et al. (Translational Stroke Research, 2025)

Assessment of a base-isolated structure with semi-active low-cost viscous fluid dampers through real-time hybrid simulations - S. Vides; B. Castillo; A. Artunduaga; J. Marulanda; P. Thomson (Innovative Infrastructure Solutions, 2025)
The dynamic performance of low-rise buildings under dynamic loads presents significant challenges in structural engineering. Accurate evaluation methods are crucial for ensuring the safety and resilience of these structures, especially in seismic-prone areas. This study focuses on implementing Real-Time Hybrid Simulations (RTHS) for the assessment of structural control systems in low-rise buildings. The research integrates a numerical substructure, which models the dynamic characteristics of the building, with an experimental substructure that consists of physical devices such as base isolators, semi-active fluid viscous dampers, or hybrid control system. The RTHS method provides a sophisticated platform to evaluate the effectiveness of hybrid control systems under seismic excitations. The results demonstrated a marked improvement in predicting structural responses, with the proposed method achieving a 15.0% reduction in error compared to fixed structure. Additionally, the application of hybrid control systems showed a 25.0% increase in energy dissipation capacity compared to individual passive control. These findings contribute to the advancement of resilient design strategies, offering a quantitative framework for optimizing structural control systems in low-rise buildings.

Metro Manila households’ willingness to pay for renewable energy as a climate change mitigation measure: a CVM study - Rosalina Palanca-Tan; Masahiro Sugiyama; Daniel del Barrio Alvarez; Gem B. Castillo; Nelson Matthew P. Tan (Sustainability Science, 2025)

NOTCH3 Variant Position Affects the Phenotype at the Pluripotent Stem Cell Level in CADASIL - Ana Bugallo-Casal; Elena Muiño; Susana B. Bravo; Pablo Hervella; Susana Arias-Rivas; Manuel Rodríguez-Yáñez; Enrique Vara-León; Rita Quintas-Rey; Lara Pérez-Gayol; Olga Maisterra-Santos; Jesús Pizarro-Gonzálvez; María Rosa Martorell-Riera; et al. (NeuroMolecular Medicine, 2025)

Bee pollination affects coffee quality, yield, and trade-offs within them - Natalia Aristizábal; Silvia E. Mora-Mena; Alejandra Martínez-Salinas; Adina Chain-Guadarrama; Danny Castillo; Juan B. Murillo; Jimmy Porras; Taylor H. Ricketts (Agriculture, Ecosystems & Environment, 2025)

Early‐Stage Extratropical Cyclones' Mechanisms Over South America: RCM Added Value and Future Changes in a Warmer Planet - Carolina B. Gramcianinov; Andressa A. Cardoso; Natália P. da Silva; Rosa Luna‐Niño; Natalia Castillo; Tereza Cavazos; Rosmeri P. da Rocha (International Journal of Climatology, 2025)
Regional climate models (RCMs) from the CORDEX enable further investigations of the regional aspects of climate change impacts in South America. Here, we assess the CORDEX‐RCMs' present and future projections of extratropical cyclones, focusing on their frequency, early‐stage synoptic features, and added value relative to the global climate models (GCMs). Cyclones were tracked using a common algorithm in the present (1985–2005) and future RCP8.5 scenarios (2080–2099). ERA5 reanalysis was used as reference data in the present climate. Both GCMs and RCMs can identify the three major cyclone hot spots in South America: Argentina (ARG), La Plata Basin (LPB), and the south‐southeast Brazilian coast (SBR). RCMs improve GCMs' representation of the cyclogenesis frequency, adding value by decreasing the biases (~10%). Early‐stage cyclone synoptic structure also indicates RCMs' improvement of the low‐level fields by presenting mesoscale structures of warm/cold advection and moisture flux convergence/divergence in greater agreement with ERA5 (except for moisture flux divergence for LPB). RCMs and GCMs project a general decrease in cyclogenesis for the end of the century. For the cyclogenesis cores, GCMs' and RCMs' projections agree on the trend signals in SBR, LPB, and ARG in austral winter and disagree in ARG in austral summer. For LPB and SBR cyclogenesis, the RCMs and GCMs suggest a future increase in moisture flux convergence and warm advection at low levels, while a decrease in upper level divergence is projected. This indicates a reinforcement of cyclogenesis (negative sea‐level pressure trend) in the future due to the low‐level features and associated diabatic processes. For ARG, the future trends in the mean structure of cyclogenesis are relatively weak. Following other studies, cyclogenesis frequency may decrease; however, changes could occur in some important physical processes, such as low‐level moisture flux convergence and warm advection, suggesting more intense events in the future.

Cadmium availability in rhizosphere and non-rhizosphere soils in cacao farms in Santander, Colombia - C. A. Adarme-Duran; J. Ágreda; P. F. B. Brandão; E. Castillo (Environmental Monitoring and Assessment, 2024)
Current research has highlighted the need to understand the factors influencing cadmium (Cd) availability in cacao-growing soils to elucidate its presence in cacao beans (the raw material for chocolate). Although literature about this topic is increasing, few report the importance of rhizosphere soils on Cd dynamics. This study aimed to understand the changes in available Cd and its association with soil properties (pH, pseudo-total Cd, available Cd (Cd-DTPA), Ca, Mg, K, Na, soil organic carbon, P, Zn, urease activity, exchangeable acidity, and cation exchange capacity) considering rhizosphere and non-rhizosphere soils. Both soil types (51 samples of each, 102 in total) were collected from two Colombian cacao farms. The medians of pseudo-total Cd (1.86 mg kg −1 ) and Cd-DTPA (0.76 mg kg −1 ) were, respectively, about threefold and fourfold higher in rhizosphere compared to non-rhizosphere soils. Principal component analysis showed a clear distinction between rhizosphere and non-rhizosphere soils based on differences in soil properties, which explained the observed changes in available Cd when comparing both soil types. Soil organic carbon and Zn were important drivers of available Cd in rhizosphere soils. Spatial distribution analysis revealed a tendency of available Cd to cluster in rhizosphere soils, and indicated hotspots within each farm. These findings highlight the importance of rhizosphere soils for Cd diagnosis and monitoring, and for improving knowledge about Cd dynamics in the soil- Theobroma cacao L. system.

Genomic Vulnerability to Climate Change of an Australian Migratory Freshwater Fish, the Golden Perch ( Macquaria ambigua ) - Emily J. Booth; Chris J. Brauer; Jonathan Sandoval‐Castillo; Katherine Harrisson; Meaghan L. Rourke; Catherine R.M. Attard; Dean M. Gilligan; Zeb Tonkin; Jason D. Thiem; Peter J. Unmack; Brenton Zampatti; Luciano B. Beheregaray (Molecular Ecology, 2024)
Genomic vulnerability is a measure of how much evolutionary change is required for a population to maintain optimal genotype‐environment associations under projected climates. Aquatic species, and in particular migratory ectotherms, are largely underrepresented in studies of genomic vulnerability. Such species might be well equipped for tracking suitable habitat and spreading diversity that could promote adaptation to future climates. We characterised range‐wide genomic diversity and genomic vulnerability in the migratory and fisheries‐important golden perch ( Macquaria ambigua ) from Australia's expansive Murray–Darling Basin (MDB). The MDB has a steep hydroclimatic gradient and is one of the world's most variable regions in terms of climate and streamflow. Golden perch are threatened by fragmentation and obstruction of waterways, alteration of flow regimes, and a progressively hotter and drying climate. We gathered a genomic dataset of 1049 individuals from 186 MDB localities. Despite high range‐wide gene flow, golden perch in the warmer, northern catchments had higher predicted vulnerability than those in the cooler, southern catchments. A new cross‐validation approach showed that these predictions were insensitive to the exclusion of individual catchments. The results raise concern for populations at warm range edges, which may already be close to their thermal limits. However, a population with functional variants beneficial for climate adaptation found in the most arid and hydrologically variable catchment was predicted to be less vulnerable. Native fish management plans, such as captive breeding and stocking, should consider spatial variation in genomic vulnerability to improve conservation outcomes under climate change, even for dispersive species with high connectivity.

Theoretical and experimental study of adsorption and catalytic reactivity of asphaltene fractions A1 and A2 over cubic NiO–PdO/CeO2 nanoparticles - Oscar E. Medina; Ivan Moncayo Riascos; Samira Heidari; Sócrates A. Acevedo; Jimmy Castillo; Farid B. Cortés; Camilo A. Franco (Fuel, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Connecting the dots: Applying multispecies connectivity in marine park network planning - Katie Gates; Jonathan Sandoval-Castillo; Andrea Barceló; Andrea Bertram; Eleanor A.L. Pratt; Peter R. Teske; Luciana Möller; Luciano B. Beheregaray (Biological Conservation, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

P26-01 Hexagonal boron nitride (hBN) and hBN-reinforced thermoplastic polyurethane composite: an in vitro hazard characterization using human skin and lung cells - M. Carlin; J. Kaur; D.Z. Ciobanu; Z. Song; M. Olsson; T. Totu; G. Gupta; G. Peng; V. Jehová González; I.J. Janica; V. Fuster Pozo; S. Chortarea; et al. (Toxicology Letters, 2024)

P18-09 Quantitative analysis of micro and nanoplastics in biological tissues: implications for environmental and human health - M. Garcia; A. Nihart; R. Liu; E. El Hayek; E. Castillo; B. Bleske; E. Barrozo; M.A. Suter; J. Scott; K. Forsythe; N. Adolfi; D. Gallego Umana; et al. (Toxicology Letters, 2024)

Genetic and phenotypic differentiation in functional traits of Iris pseudacorus L. in native and introduced Mediterranean climate ranges - B. Gallego-Tévar; B. J. Grewell; J. F. Gaskin; J. M. Castillo (Biological Invasions, 2024)
Intraspecific variation in functional traits between native and introduced plant species may underlie resilience and invasiveness of introduced species. We explored if observed phenotypic variation of Iris pseudacorus L. between populations in the native vs. introduced ranges results from genetic differentiation and/or phenotypic plasticity. Seeds were collected from populations along estuarine stress gradients within populations in both Guadalquivir Estuary (Andalusia, Spain) and San Francisco Bay-Delta Estuary (California, USA). Genetic analysis was performed on leaf tissue from plants in each seed donor population. Germinants (n = 48: 6 plants × 4 populations × 2 ranges) were grown for 12 months in a common garden experiment (CGE). We then evaluated 25 traits including growth, biomass allocation, morphological and biochemical responses. Geographic range explained relative intraspecific trait variation segregating native from introduced phenotypes. Native plants had lower specific leaf area (− 34%) and carbohydrate concentrations in rhizomes (− 63%) than introduced plants, providing evidence of genetic differentiation. Higher genetic diversity and 27% higher phenotypic variation (CGE) of native vs. introduced plants indicated longer-term adaptive processes in the native range. Genetic distance of introduced populations (field) increased along with their phenotypic distance (CGE), suggesting rapid genetic differentiation. Phenotypic plasticity also explained some observed inter-range differences under field conditions not expressed by plants in the CGE. Management of the introduced I. pseudacorus populations should be established urgently since they represent novel genotypes with key functional traits that can support invasiveness through increased competitive ability and physiological stress tolerances to sea level rise.

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Impacts of climate-driven upwelling intensification on the microbiota and health of cultivated scallops - Roxana González; Carlos Henríquez-Castillo; Karin B. Lohrmann; Rosanna Rojas; Ana Mercado; Germán Lira; Katherina Brokordt (Aquaculture, 2024)

Hazard assessment of hexagonal boron nitride and hexagonal boron nitride reinforced thermoplastic polyurethane composites using human skin and lung cells - Michela Carlin; Jasreen Kaur; Dinu Zinovie Ciobanu; Zhengmei Song; Magnus Olsson; Tiberiu Totu; Govind Gupta; Guotao Peng; Viviana Jehová González; Iwona Janica; Victor Fuster Pozo; Savvina Chortarea; et al. (Journal of Hazardous Materials, 2024)

What if there is no further south to go: Assessing the vulnerability of Nacella species to climate change - Paola B. Reyna; Santiago Castillo; M. Carla de Aranzamendi (Estuarine, Coastal and Shelf Science, 2024)

Metamodeling-based reliability analysis framework for activated sludge processes - R.A. Borobio-Castillo; J.M. Cabrera-Miranda; B. Corona-Vásquez (Water Research, 2024)

A global analysis of field body temperatures of active squamates in relation to climate and behaviour - Shahar Dubiner; Rocío Aguilar; Rodolfo O. Anderson; Diego M. Arenas Moreno; Luciano J. Avila; Estefania Boada‐Viteri; Martin Castillo; David G. Chapple; Christian O. Chukwuka; Alison Cree; Félix B. Cruz; Guarino R. Colli; et al. (Global Ecology and Biogeography, 2024)
Aim Squamate fitness is affected by body temperature, which in turn is influenced by environmental temperatures and, in many species, by exposure to solar radiation. The biophysical drivers of body temperature have been widely studied, but we lack an integrative synthesis of actual body temperatures experienced in the field, and their relationships to environmental temperatures, across phylogeny, behaviour and climate. Location Global (25 countries on six continents). Taxa Squamates (210 species, representing 25 families). Methods We measured the body temperatures of 20,231 individuals of squamates in the field while they were active. We examined how body temperatures vary with substrate and air temperatures across taxa, climates and behaviours (basking and diel activity). Results Heliothermic lizards had the highest body temperatures. Their body temperatures were the most weakly correlated with substrate and air temperatures. Body temperatures of non‐heliothermic diurnal lizards were similar to heliotherms in relation to air temperature, but similar to nocturnal species in relation to substrate temperatures. The correlation of body temperature with air and substrate temperatures was stronger in diurnal snakes and non‐heliothermic lizards than in heliotherms. Body‐substrate and body‐air temperature correlations varied with mean annual temperatures in all diurnal squamates, especially in heliotherms. Thermal relations vary with behaviour (heliothermy, nocturnality) in cold climates but converge towards the same relation in warm climates. Non‐heliotherms and nocturnal species body temperatures are better explained by substrate temperature than by air temperature. Body temperature distributions become left‐skewed in warmer‐bodied species, especially in colder climates. Main Conclusions Squamate body temperatures, their frequency distributions and their relation to environmental temperature, are globally influenced by behavioural and climatic factors. For all temperatures and climates, heliothermic species' body temperatures are consistently higher and more stable than in other species, but in regions with warmer climate these differences become less pronounced. A comparable variation was found in non‐heliotherms, but in not nocturnal species whose body temperatures were similar to air and substrate irrespective of the macroclimatic context.

Straw digestibility in rice: Novel insights from pyrolysis GC-MS and biomass phenotyping - Mariana P. Silva; Caragh Whitehead; Reynante L. Ordonio; Trinidad C. Fernando; Mark Philip B. Castillo; Jeremias L. Ordonio; Tony Larson; Daniel J. Upton; Susan E. Hartley; Leonardo D. Gomez (Biomass and Bioenergy, 2024)

Monitoring of Chemical Species in Soils, Waters and Plants Near the Active Copper Mine Tailing Dam Ovejeria (Central Chile) - Y. Tapia; A. García; E. Acuña; O. Salazar; M. Casanova; F. Najera; C. Kremer; B. Castillo; A. Joven; O. Diaz; R. Pastene; M. Antilen; et al. (Water, Air, & Soil Pollution, 2024)

PHB production by Bacillus megaterium strain MNSH1-9K-1 using low-cost media - Andrea M. Rivas-Castillo; Alejandro Valdez-Calderón; Arturo F. Angeles-Padilla; César B. Figueroa-Ocampo; Sandra Carrillo-Ibarra; Maribel Quezada-Cruz; Arian Espinosa-Roa; Brandon D. Pérez-García; Norma G. Rojas-Avelizapa (Brazilian Journal of Microbiology, 2024)

Effectiveness of dietary heat-killed Bacillus subtilis harboring plasmid containing 60 copies of CpG-ODN 1668 against Vibrio harveyi in Penaeus vannamei - Wahyu Purbiantoro; Vinh Huynh-Phuoc; B. R. J. Castillo-Corea; Omkar Vijay Byadgi; Ta-Chih Cheng (Veterinary Research Communications, 2024)

Potential ecological risk assessment of microplastics in coastal sediments: Their metal accumulation and interaction with sedimentary metal concentration - Azenith B. Castillo; Marwa El-Azhary; Caesar Sorino; Lewis LeVay (Science of The Total Environment, 2024)

Ecological indicators and source diagnostic ratios of aliphatic and polyaromatic hydrocarbons in marine sediments of Qatar - Maryam A. Abdulla; Azenith B. Castillo; Christopher Collins; Tom Sizmur (Regional Studies in Marine Science, 2023)

A multi-stage Bayesian modelling for building the chronocultural sequence of the Late Mesolithic at Cueva de la Cocina (Valencia, Eastern Iberia) - Oreto García-Puchol; Sarah B. McClure; Joaquim Juan-Cabanilles; Alfredo Cortell-Nicolau; Agustín Diez-Castillo; Josep Lluís Pascual Benito; Manuel Pérez-Ripoll; Salvador Pardo-Gordó; Gianni Gallello; Mirco Ramacciotti; Lluís Molina- Balaguer; Esther López-Montalvo; et al. (Quaternary International, 2023)

Leaching tests reveal fast aluminum fluoride release from ashfall accumulated in La Palma (Canary Islands, Spain) after the 2021 Tajogaite eruption - J. Sánchez-España; M. Pilar Mata; J. Vegas; G. Lozano; J. Mediato; J. Martínez Martínez; I. Galindo; N. Sánchez; B. del Moral; B. Ordóñez; A. de Vergara; A. Nieto; et al. (Journal of Volcanology and Geothermal Research, 2023)

Contrasting patterns of land-cover change between early and late successional forests in a tropical montane cloud forest area managed under the milpa system - Ernesto de los Santos-Reyes; Rafael F. del Castillo; Matthias Rös; David B. Bray (Forest Ecology and Management, 2023)

Influence of Krill Meal on the Performance of Post-Smolt Atlantic Salmon That Are Fed Plant-Based and Animal-Based Fishmeal and Fish Oil-Free Diets - Frederick T. Barrows; Kelly B. Campbell; T. Gibson Gaylord; Rodrigo C. M. Sanchez; Sergio A. Castillo; Ewen McLean (Fishes, 2023)
The purpose of this study was to determine the influence of krill meal (KM) inclusion at various levels (0%, 2.5%, 5%) in plant-based and animal-based feeds, that were fishmeal (FM) and fish oil (FO) free, on Atlantic salmon growth. A FM/FO feed containing 0% KM was the control. Using a 2 × 3 factorial approach, diets were randomly assigned to one of 28 0.5 m3 flow-through tanks (n = 4 tanks per diet) initially stocked with 60 fish (148.4 ± 12.9 g; 23.6 ± 0.8 cm; condition factor (K) = 1.16 ± 0.08) each. Salmon were fed for 90 days using automatic feeders ad libitum. On day 45, stocking densities were reduced to 45 fish per tank by the random removal of 15 individuals to remove any potential of density affecting growth through the trial end. Water temperature, oxygen saturation, pH, and salinity throughout the trial were 11.8 °C, 103.5%, 7.38, and 32.0 g L−1, respectively. Fish fed plant-based feed without KM were lighter (p 0.05) to the control and 5% KM plant-based groups, with KM increasing feed intake (p

Multiple dimensions of extreme weather events and their impacts on biodiversity - Juan David González-Trujillo; Rosa M. Román-Cuesta; Aarón Israel Muñiz-Castillo; Cibele H. Amaral; Miguel B. Araújo (Climatic Change, 2023)
Climate change is a multidimensional phenomenon. As such, no single metric can capture all trajectories of change and associated impacts. While numerous metrics exist to measure climate change, they tend to focus on central tendencies and neglect the multidimensionality of extreme weather events (EWEs). EWEs differ in their frequency, duration, and intensity, and can be described for temperature, precipitation, and wind speed, while considering different thresholds defining “extremeness.” We review existing EWE metrics and outline a framework for classifying and interpreting them in light of their foreseeable impacts on biodiversity. Using an example drawn from the Caribbean and Central America, we show that metrics reflect unequal spatial patterns of exposure across the region. Based on available evidence, we discuss how such patterns relate to threats to biological populations, empirically demonstrating how ecologically informed metrics can help relate EWEs to biological processes such as mangrove recovery. Unveiling the complexity of EWE trajectories affecting biodiversity is only possible through mobilisation of a plethora of climate change metrics. The proposed framework represents a step forward over assessments using single dimensions or averages of highly variable time series.

Exposure to secondhand and thirdhand smoke in private vehicles: Measurements in air and dust samples - Xavier Continente; Elisabet Henderson; Laura López-González; Esteve Fernández; Olena Tigova; Sean Semple; Rachel O'Donnell; Ana Navas-Acién; Núria Cortés-Francisco; Noelia Ramírez; Ruaraidh Dobson; Maria José López; et al. (Environmental Research, 2023)

Ecological aspects of false killer whales ( Pseudorca crassidens ) from Mexican Pacific and Southern California waters - Camila Lazcano‐Pacheco; Acilegna J. Castillo‐Sánchez; Christian D. Ortega‐Ortiz; Ibiza Martínez‐Serrano; Francisco Villegas‐Zurita; Astrid Frisch‐Jordán; Oscar R. Guzón‐Zatarain; Katherina Audley; Nicola Ransome; Jaime Bolaños‐Jiménez; Jorge Urbán‐R.; Annie B. Douglas (Marine Mammal Science, 2023)

Observation of large scale precursor correlations between cosmic rays and earthquakes with a periodicity similar to the solar cycle - P. Homola; V. Marchenko; A. Napolitano; R. Damian; R. Guzik; D. Alvarez-Castillo; S. Stuglik; O. Ruimi; O. Skorenok; J. Zamora-Saa; J.M. Vaquero; T. Wibig; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Community Patterns and Environmental Associations for the Early Life Stages of Fishes in a Highly Transformed Estuary - Gonzalo C. Castillo; Trishelle Tempel; Steven B. Slater; Brian Mahardja; Morgan D. Gilbert (Estuaries and Coasts, 2023)
Estuaries are important fish nursery areas, yet little is known of how environmental forcing influences estuarine fishes during their early life stages. We analyzed environmental and larval-juvenile fish community data in the upper San Francisco Estuary (SFE) from spring to early summer 1995–2017, to better understand drivers of spatiotemporal community patterns in this highly modified estuary. We evaluated community patterns based on the relative abundance and diversity of native and introduced fish in the SFE and their predominant distribution (pelagic, demersal). The upper SFE experienced a downward trend of freshwater outflow and upward trends of temperature and salinity intrusion. Fish relative abundance only showed long-term downtrends for native and introduced pelagic fish groups. The most influential habitat components for relative abundance and diversity of fish groups were in decreasing order: temperature, salinity, Secchi depth, bottom depth, and zooplankton biomass. Early life stages of native and introduced fishes were generally segregated spatially and temporally, with native fishes more associated with cooler, saltier, and higher turbidity habitats during early to mid-spring compared to introduced fishes during late spring to early summer. Community ordination showed that environmental (temperature, salinity, outflow, Secchi depth, and zooplankton biomass) and spatiotemporal factors (month and depth), explained nearly 40% of the total variance. Our results suggest that the shorter duration of planktonic and nektonic stages of demersal fish groups results in higher resiliency compared to pelagic fishes. The declining abundance of pelagic fishes overall seems to be linked to drought effects and human-induced synergistic interactions intensified by climate change.

A critical thermal transition driving spring phenology of Northern Hemisphere conifers - Jian‐Guo Huang; Yaling Zhang; Minhuang Wang; Xiaohan Yu; Annie Deslauriers; Patrick Fonti; Eryuan Liang; Harri Mäkinen; Walter Oberhuber; Cyrille B. K. Rathgeber; Roberto Tognetti; Václav Treml; et al. (Global Change Biology, 2023)
Despite growing interest in predicting plant phenological shifts, advanced spring phenology by global climate change remains debated. Evidence documenting either small or large advancement of spring phenology to rising temperature over the spatio‐temporal scales implies a potential existence of a thermal threshold in the responses of forests to global warming. We collected a unique data set of xylem cell‐wall‐thickening onset dates in 20 coniferous species covering a broad mean annual temperature (MAT) gradient (−3.05 to 22.9°C) across the Northern Hemisphere (latitudes 23°–66° N). Along the MAT gradient, we identified a threshold temperature (using segmented regression) of 4.9 ± 1.1°C, above which the response of xylem phenology to rising temperatures significantly decline. This threshold separates the Northern Hemisphere conifers into cold and warm thermal niches, with MAT and spring forcing being the primary drivers for the onset dates (estimated by linear and Bayesian mixed‐effect models), respectively. The identified thermal threshold should be integrated into the Earth‐System‐Models for a better understanding of spring phenology in response to global warming and an improved prediction of global climate‐carbon feedbacks.

Water-rich C-type asteroids as early solar system carbonate factories - Victoria Froh; Maitrayee Bose; Martin D. Suttle; Jacopo Nava; Luigi Folco; Lynda B. Williams; Julie Castillo-Rogez (Icarus, 2023)

Measurement of airborne nicotine, as a marker of secondhand smoke exposure, in homes with residents who smoke in 9 European countries - Elisabet Henderson; Luis A. Rodriguez Guerrero; Xavier Continente; Esteve Fernández; Olena Tigova; Nuria Cortés-Francisco; Sean Semple; Ruaraidh Dobson; Anna Tzortzi; Vergina K. Vyzikidou; Giuseppe Gorini; Gergana Geshanova; et al. (Environmental Research, 2023)

Exposure to secondhand aerosol from electronic cigarettes at homes: A real-life study in four European countries - Beladenta Amalia; Marcela Fu; Olena Tigova; Montse Ballbè; Blanca Paniello-Castillo; Yolanda Castellano; Vergina K. Vyzikidou; Rachel O'Donnell; Ruaraidh Dobson; Alessandra Lugo; Chiara Veronese; Raúl Pérez-Ortuño; et al. (Science of The Total Environment, 2023)

Hydrogeochemical and isotopic signatures elucidate deep subsurface hypersaline brine formation through radiolysis driven water-rock interaction - D.M. Nisson; T.L. Kieft; H. Drake; O. Warr; B. Sherwood Lollar; H. Ogasawara; S.M. Perl; B.M. Friefeld; J. Castillo; M.J. Whitehouse; E. Kooijman; T.C. Onstott (Geochimica et Cosmochimica Acta, 2023)

Nitrogen and phosphorus budget in an intensive irrigation area and effects on littoral water and groundwater (Yaqui Valley, Northwestern Mexico) - B. R. Almazán; M. V. Esteller; S. E. Garrido-Hoyos; J. L. Expósito-Castillo; C. Díaz-Delgado; J. C. García-Colín (Environmental Monitoring and Assessment, 2023)

Molecular insights into the invasion dynamics of Carcinus crabs in South Africa - Clova A. Mabin; Tamara B. Robinson; John R. U. Wilson; Heidi Hirsch; Maria L. Castillo; Michelle Jooste; Johannes J. Le Roux (Biological Invasions, 2022)
Knowledge of the introduction history and spread dynamics of invasive species can provide important insights for management (Ens et al. in Environ Rev (in press), 2022), however such information is often unavailable for accidental introductions. Here we infer how the European shore crab, Carcinus maenas , and its congener, the Mediterranean shore crab, C. aestuarii , were introduced to and spread within South Africa. We do this using nuclear microsatellite data and Bayesian assignment tests and Approximate Bayesian Computation (ABC) modelling that included samples from the native and other invasive ranges of these two species. We also compared the genetic diversity and structure of one of the South African populations during and after intensive management, with that of another, unmanaged, population. South African populations had higher genetic diversity than invasive Carcinus populations from elsewhere in the world. Moreover, the ABC analyses suggest that South African populations originated from an admixture event between individuals of C. maenas from a population in the native range and an invasive population from Canada. We also identified instances of hybridisation between Carcinus maenas and C. aestuarii in South Africa. South African populations showed no genetic structure, suggesting either extensive migration between them or that populations arose from the same initial introduction. Management of Carcinus did not affect genetic diversity or structure, and we suspect that the management duration was insufficient to target a full generation of crabs. Together these results suggest multiple introductions and/or high propagule pressure to South Africa, crab (larval or adult) movement between existing populations, and some hybridisation. For eradication from South Africa to be achieved, management would need to concurrently target all known invasive populations and clearly establish that new introductions could be prevented.

Mosquito control opportunities amid regulations within the tidal marshes of the San Francisco Bay Area - Erika B. Castillo; Ryan J. Clausnitzer; Eric J. Haas-Stapleton (Wetlands Ecology and Management, 2022)

Reversible mutations in gliding motility and virulence genes: A flexible and efficient phage defence mechanism in Flavobacterium psychrophilum - Jóhanna Jørgensen; Krister Sundell; Daniel Castillo; Liv S. Dramshøj; Natasja B. Jørgensen; Susie B. Madsen; Lotta Landor; Tom Wiklund; Valentina L. Donati; Lone Madsen; Inger Dalsgaard; Mathias Middelboe (Environmental Microbiology, 2022)
Flavobacteria are among the most important pathogens in freshwater salmonid aquaculture worldwide. Due to concerns regarding development of antibiotic resistance, phage therapy has been proposed as a solution to decrease pathogen load. However, application of phages is challenged by the development of phage resistance, and knowledge of the mechanisms and implications of phage resistance is therefore required. To study this, 27 phage‐resistant isolates of F. psychrophilum were genome sequenced and characterized to identify genetic modifications and evaluate changes in phenotypic traits, including virulence against rainbow trout. Phage‐resistant isolates showed reduction or loss of gliding motility, proteolytic activity, and adhesion to surfaces, and most isolates were completely non‐virulent against rainbow trout fry. Genomic analysis revealed that most phage‐resistant isolates had mutations in genes associated with gliding motility and virulence. Reversal of these mutations in a sub‐set of isolates led to regained motility, proteolytic activity, virulence and phage susceptibility. Although costly, the fast generation of phage resistance driven by single, reversible mutations likely represents a flexible and efficient phage defence mechanism in F. psychrophilum . The results further suggest that phage administration in aquaculture systems to prevent F. psychrophilum outbreaks selects for non‐virulent phage‐resistant phenotypes.

Aridification‐driven evolution of a migratory fish revealed by niche modelling and coalescence simulations - Emily J. Booth; Jonathan Sandoval‐Castillo; Catherine R. M. Attard; Dean M. Gilligan; Peter J. Unmack; Luciano B. Beheregaray (Journal of Biogeography, 2022)
Aim Major knowledge gaps exist regarding the evolution of arid zone organisms. For freshwater species with high dispersal potential, little is known if historical aridification influenced connectivity across drainage divides and impacted on their divergence and diversification. We tested the hypothesis that the historical aridification of Australia promoted the isolation and influenced the demographic histories and evolutionary divergence of a migratory group of freshwater obligates. Location Central and eastern Australia; Murray–Darling Basin (MDB), Lake Eyre Basin (LEB), Fitzroy Basin (FIT). Taxon Three lineages of golden perch ( Macquaria ambigua ), a widespread fishery resource from inland Australia. Methods We obtained genome‐wide data for golden perch sampled throughout their range. Phylogenetic relationships were reconstructed using maximum likelihood. Species distribution modelling was used to predict contemporary and past distributions for the three lineages and to develop hypotheses regarding their biogeographic and demographic histories. Hypotheses were independently tested using coalescent simulations in fastsimcoal and DIYABC with the genomic dataset. Results We found evidence for three reciprocally monophyletic lineages that have experienced little to nil genetic connectivity since divergence. Coalescent models suggest that the coastal (FIT) and inland (MDB and LEB) lineages diverged ~103 thousand years ago (ka), followed by the split of MDB and LEB lineages ~58 ka. These timings agree with reductions of large freshwater environments in Australia during the late Pleistocene. Species distribution models show an extreme decrease in habitat during the Last Glacial Maximum ~21 ka, consistent with inferred demographic contractions in coalescent tests. Main conclusions We reveal that aridification of Australia during the late Pleistocene has driven and reinforced the divergence of a migratory freshwater obligate. Our findings are important for informing the conservation management of aquatic organisms under climate change. This work further demonstrates the value of using species distribution modelling to formulate diversification hypotheses and to improve interpretation of coalescent analyses.

Extinction risk, reconstructed catches and management of chondrichthyan fishes in the Western Central Atlantic Ocean - Brendan S. Talwar; Brooke Anderson; Cristopher G. Avalos‐Castillo; María del Pilar Blanco‐Parra; Alejandra Briones; Diego Cardeñosa; John K. Carlson; Patricia Charvet; Charles F. Cotton; Zoe Crysler; Danielle H. Derrick; Michael R. Heithaus; et al. (Fish and Fisheries, 2022)
Chondrichthyan fishes are among the most threatened vertebrates on the planet because many species have slow life histories that are outpaced by intense fishing. The Western Central Atlantic Ocean, which includes the Greater Caribbean, is a hotspot of chondrichthyan biodiversity and abundance, but has been characterized by extensive shark and ray fisheries and a lack of sufficient data for effective management and conservation. To inform future research and management decisions, we analysed patterns in chondrichthyan extinction risk, reconstructed catches and management engagement in this region. We summarized the extinction risk of 180 sharks, rays and chimaeras, including 66 endemic and 14 near‐endemic species, using contemporary IUCN Red List assessments. Over one‐third (35.6%) were assessed as Vulnerable, Endangered or Critically Endangered, primarily due to overfishing. Reconstructed catches from 1950 to 2016 peaked in 1992, then declined by 40.2% thereafter. The United States, Venezuela and Mexico were responsible for most catches in the region and hosted the largest proportions of the regional distributions of threatened species, largely due to having extensive coastal habitats in their Exclusive Economic Zones. The quantity and taxonomic resolution of fisheries landings data were poor in much of the region, and national‐level regulations varied widely across jurisdictions. Deepwater fisheries represent an emerging threat, although many deepwater chondrichthyans currently have refuge beyond the depths of most fisheries. Regional collaboration as well as effective and enforceable management informed by more complete fisheries data, particularly from small‐scale fisheries, are required to protect and recover threatened species and ensure sustainable fisheries.

Physicochemical Control of Caribbean Coral Calcification Linked to Host and Symbiont Responses to Varying pCO2 and Temperature - Robert A. Eagle; Maxence Guillermic; Illian De Corte; Blanca Alvarez Caraveo; Colleen B. Bove; Sambuddha Misra; Louise P. Cameron; Karl D. Castillo; Justin B. Ries (Journal of Marine Science and Engineering, 2022)
It is thought that the active physiological regulation of the chemistry of a parent fluid is an important process in the biomineralization of scleractinian corals. Biological regulation of calcification fluid pH (pHCF) and other carbonate chemistry parameters ([CO32−]CF, DICCF, and ΩCF) may be challenged by CO2 driven acidification and temperature. Here, we examine the combined influence of changing temperature and CO2 on calcifying fluid regulation in four common Caribbean coral species—Porites astreoides, Pseudodiploria strigosa, Undaria tenuifolia, and Siderastrea siderea. We utilize skeletal boron geochemistry (B/Ca and δ11B) to probe the pHCF, [CO32−]CF, and DICCF regulation in these corals, and δ13C to track changes in the sources of carbon for calcification. Temperature was found to not influence pHCF regulation across all pCO2 treatments in these corals, in contrast to recent studies on Indo-Pacific pocilloporid corals. We find that [DIC]CF is significantly lower at higher temperatures in all the corals, and that the higher temperature was associated with depletion of host energy reserves, suggesting [DIC]CF reductions may result from reduced input of respired CO2 to the DIC pool for calcification. In addition, δ13C data suggest that under high temperature and CO2 conditions, algal symbiont photosynthesis continues to influence the calcification pool and is associated with low [DIC]CF in P. strigosa and P. astreoides. In P. astreoides this effect is also associated with an increase in chlorophyll a concentration in coral tissues at higher temperatures. These observations collectively support the assertion that physicochemical control over coral calcifying fluid chemistry is coupled to host and symbiont physiological responses to environmental change, and reveals interspecific differences in the extent and nature of this coupling.

Alpinumisoflavone against cancer pro-angiogenic targets: In silico, In vitro, and In ovo evaluation - Honeymae C. Alos; Junie B. Billones; Agnes L. Castillo; Ross D. Vasquez (DARU Journal of Pharmaceutical Sciences, 2022)

Seascape genomics of coastal bottlenose dolphins along strong gradients of temperature and salinity - Eleanor A. L. Pratt; Luciano B. Beheregaray; Kerstin Bilgmann; Nikki Zanardo; Fernando Diaz‐Aguirre; Chris Brauer; Jonathan Sandoval‐Castillo; Luciana M. Möller (Molecular Ecology, 2022)
Heterogeneous seascapes and strong environmental gradients in coastal waters are expected to influence adaptive divergence, particularly in species with large population sizes where selection is expected to be highly efficient. However, these influences might also extend to species characterized by strong social structure, natal philopatry and small home ranges. We implemented a seascape genomic study to test this hypothesis in Indo‐Pacific bottlenose dolphins ( Tursiops aduncus ) distributed along the environmentally heterogeneous coast of southern Australia. The data sets included oceanographic and environmental variables thought to be good predictors of local adaptation in dolphins and 8081 filtered single nucleotide polymorphisms (SNPs) genotyped for individuals sampled from seven different bioregions. From a neutral perspective, population structure and connectivity of the dolphins were generally influenced by habitat type and social structuring. Genotype‐environment association analysis identified 241 candidate adaptive loci and revealed that sea surface temperature and salinity gradients influenced adaptive divergence in these animals at both large‐ (1000 km) and fine‐scales (

Genomics outperforms genetics to manage mistakes in fisheries stocking of threatened species - Catherine R. M. Attard; Jonathan Sandoval-Castillo; Dean M. Gilligan; Peter J. Unmack; Leanne K. Faulks; Luciano B. Beheregaray (Biodiversity and Conservation, 2022)
Hatchery production and fisheries stocking is a widespread and high profile management practice because it allows recreational fisheries to continue in threatened species. Human-mediated transfer of fish across the geographic boundaries of intraspecies lineages or closely related species can cause introgression and occasionally outbreeding depression. Hybridization can be difficult to detect due to limited morphological differences among close lineages and the relatively low power of traditional genetic datasets. Here we showcase the use of genomic techniques to detect admixture of the economically important and threatened golden perch ( Macquaria ambigua ) in the Murray-Darling Basin, southeast Australia. We detected admixture through a genome-wide dataset of 6,862 single nucleotide polymorphisms (SNPs) across 174 Murray-Darling sourced fish and 15 fish from each of two neighbouring basins: the Lake Eyre and Fitzroy basins. Individuals with partial ancestry from both neighboring basins were detected using genomics throughout the Murray-Darling, suggesting the release of individuals and introgression into the Murray-Darling Basin. Importantly, a traditional microsatellite dataset was unreliable for identifying admixed individuals. The SNP-detected admixed individuals were also found in Murray-Darling impoundments, where fish are solely sourced from government-managed hatcheries, suggesting that some broodstock in hatcheries might have non-endemic ancestry. Stocking programs for golden perch release over one million fingerlings each year, and so could impact the genetic variation in the wild. We advocate for using genomics to check the ancestry of broodstock and for increasing collaboration between managers and academics—as done here—to better integrate the power of genomics into biodiversity management and conservation.

Coral Recovery in the Central Mexican Pacific 20 Years after the 1997–1998 El Niño Event - Violeta Martínez-Castillo; Alma Paola Rodríguez-Troncoso; Anderson B. Mayfield; Fabián Alejandro Rodríguez-Zaragoza; Amílcar Leví Cupul-Magaña (Oceans, 2022)
El Niño–Southern Oscillation (ENSO) events are increasing globally in both frequency and strength, and they can elicit coral bleaching events. The 1997–1998 ENSO caused mass coral mortality with a 96% decline in live coral cover along the Central Mexican Pacific. However, in recent years, these sites have shown signs of recovery. We used data collected in 1997 and 2015–2017 to evaluate the coral recovery in this region and coral cover levels have now reached 50% of their pre-1997–1998 El Niño values. Furthermore, a strong 2015–2016 ENSO event did not significantly affect the live coral cover, potentially demonstrating that the local corals have acclimatized or even adapted to higher temperatures. Even though branching species remain the most abundant morphotype, a PERMANOVA revealed significant changes in the coral assemblage. Collectively, this dataset is testament to the fact that corals within this region are capable of resisting or at least partially recovering from thermal anomalies caused by ENSO events.

Population genomic structure of killer whales ( Orcinus orca ) in Australian and New Zealand waters - Isabella M. Reeves; John A. Totterdell; Andrea Barceló; Jonathan Sandoval‐Castillo; Kimberley C. Batley; Karen A. Stockin; Emma L. Betty; David M. Donnelly; Rebecca Wellard; Luciano B. Beheregaray; Luciana M. Möller (Marine Mammal Science, 2022)
Population genomic data sets have enhanced power to detect cryptic and complex population structure and generate valuable information for the conservation and management of wildlife species. Globally, killer whales ( Orcinus orca ) are considered to have a complex population structure due to their ability to specialize in a variety of ecological niches. In the Australasian region, they are found year round in New Zealand waters and are sighted in all Australian waters, with seasonal aggregations in the northwest (NWA) and southwest (SWA). Regionally, there is some knowledge regarding killer whale abundance, diet, acoustics, and social structure, but limited information about their population structure. Here, we present a population structure assessment of Australasian killer whales using 17,491 high quality genome‐wide single nucleotide polymorphisms (SNPs), combined with sequences of the mitochondrial DNA control region. The results indicate a minimum of three populations: New Zealand, NWA, and SWA. These populations present moderate levels of genomic diversity, negligible levels of inbreeding, small effective population sizes, and low contemporary migration rates among them. Mitochondrial DNA analysis elucidated five closely related haplotypes, suggestive of matrilineal societies, consistent with killer whales elsewhere. This information will assist conservation management of killer whales in the Australasian region.

Whole genomes reveal multiple candidate genes and pathways involved in the immune response of dolphins to a highly infectious virus - Kimberley C. Batley; Jonathan Sandoval‐Castillo; Catherine M. Kemper; Nikki Zanardo; Ikuko Tomo; Luciano B. Beheregaray; Luciana M. Möller (Molecular Ecology, 2021)
Wildlife species are challenged by various infectious diseases that act as important demographic drivers of populations and have become a great conservation concern particularly under growing environmental changes. The new era of whole genome sequencing provides new opportunities and avenues to explore the role of genetic variants in the plasticity of immune responses, particularly in non‐model systems. Cetacean morbillivirus (CeMV) has emerged as a major viral threat to cetacean populations worldwide, contributing to the death of thousands of individuals of multiple dolphin and whale species. To understand the genomic basis of immune responses to CeMV, we generated and analysed whole genomes of 53 Indo‐Pacific bottlenose dolphins ( Tursiops aduncus ) exposed to Australia's largest known CeMV‐related mortality event that killed at least 50 dolphins from three different species. The genomic data set consisted of 10,168,981 SNPs anchored onto 23 chromosome‐length scaffolds and 77 short scaffolds. Whole genome analysis indicated that levels of inbreeding in the dolphin population did not influence the outcome of an individual. Allele frequency estimates between survivors and nonsurvivors of the outbreak revealed 15,769 candidate SNPs, of which 689 were annotated to 295 protein coding genes. These included 50 genes with functions related to innate and adaptive immune responses, and cytokine signalling pathways and genes thought to be involved in immune responses to other morbilliviruses. Our study characterised genomic regions and pathways that may contribute to CeMV immune responses in dolphins. This represents a stride towards clarifying the complex interactions of the cetacean immune system and emphasises the value of whole genome data sets in understanding genetic elements that are essential for species conservation, including disease susceptibility and adaptation.

Molecular data reveal a structured puma (Puma concolor) population in northern Patagonia, Argentina - Orlando Gallo; Diego F. Castillo; Raquel Godinho; Matías E. Mac Allister; Gabriela P. Fernández; Mauricio Failla; Emma B. Casanave (Mammalian Biology, 2021)

Integrated energy-water-land nexus planning in the Colorado River Basin (Argentina) - Thomas B. Wild; Zarrar Khan; Leon Clarke; Mohamad Hejazi; Julia Lacal Bereslawski; Micaela Suriano; Paula Roberts; José Casado; Fernando Miralles-Wilhelm; Marcelo Gavino-Novillo; Raul Muñoz-Castillo; Fekadu Moreda; et al. (Regional Environmental Change, 2021)
Integrated energy-water-land (EWL) planning promotes synergies and avoids conflicts in ways that sector-specific planning approaches cannot. Many important decisions that influence emerging EWL nexus issues are implemented at regional (e.g., large river basin, electricity grid) and sub-regional (e.g., small river basin, irrigation district) scales. However, actual implementation of integrated planning at these scales has been limited. Simply collecting and visualizing data and interconnections across multiple sectors and sub-regions in a single modeling platform is a unique endeavor in many regions. This study introduces and applies a novel approach to linking together multiple sub-regions in a single platform to characterize and visualize EWL resource use, EWL system linkages within and among sub-regions, and the EWL nexus implications of future policies and investments. This integrated planning methodology is applied in the water-stressed Colorado River Basin in Argentina, which is facing increasing demands for agricultural and fossil fuel commodities. Guided by stakeholders, this study seeks to inform basin planning activities by characterizing and visualizing (1) the basin’s current state of EWL resources, (2) the linkages between sectors within and among basin sub-regions, and (3) the EWL nexus implications of planned future agricultural development activities. Results show that water scarcity, driven in part by human demands that have historically reached 60% of total surface water supply, poses a substantial constraint to economic development in the basin. The Colorado basin has the potential to serve as a testbed for crafting novel and generalizable sub-regional EWL planning approaches capable of informing the EWL planning dialogue globally.

Salinity and inundation effects on Iris pseudacorus: implications for tidal wetland invasion with sea level rise - Brenda J. Grewell; Blanca Gallego-Tévar; Morgane B. Gillard; Caryn J. Futrell; Rebecca Reicholf; Jesús M. Castillo (Plant and Soil, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Arsenic in Latin America: New findings on source, mobilization and mobility in human environments in 20 countries based on decadal research 2010-2020 - Jochen Bundschuh; Maria Aurora Armienta; Nury Morales-Simfors; Mohammad Ayaz Alam; Dina L. López; Valeria Delgado Quezada; Sebastian Dietrich; Jerusa Schneider; Joseline Tapia; Ondra Sracek; Elianna Castillo; Lue-Meru Marco Parra; et al. (Critical Reviews in Environmental Science and Technology, 2021)

Whole-genome sequencing identifies functional noncoding variation in SEMA3C that cosegregates with dyslexia in a multigenerational family - Amaia Carrion-Castillo; Sara B. Estruch; Ben Maassen; Barbara Franke; Clyde Francks; Simon E. Fisher (Human Genetics, 2021)
Dyslexia is a common heritable developmental disorder involving impaired reading abilities. Its genetic underpinnings are thought to be complex and heterogeneous, involving common and rare genetic variation. Multigenerational families segregating apparent monogenic forms of language-related disorders can provide useful entrypoints into biological pathways. In the present study, we performed a genome-wide linkage scan in a three-generational family in which dyslexia affects 14 of its 30 members and seems to be transmitted with an autosomal dominant pattern of inheritance. We identified a locus on chromosome 7q21.11 which cosegregated with dyslexia status, with the exception of two cases of phenocopy (LOD = 2.83). Whole-genome sequencing of key individuals enabled the assessment of coding and noncoding variation in the family. Two rare single-nucleotide variants (rs144517871 and rs143835534) within the first intron of the SEMA3C gene cosegregated with the 7q21.11 risk haplotype. In silico characterization of these two variants predicted effects on gene regulation, which we functionally validated for rs144517871 in human cell lines using luciferase reporter assays. SEMA3C encodes a secreted protein that acts as a guidance cue in several processes, including cortical neuronal migration and cellular polarization. We hypothesize that these intronic variants could have a cis -regulatory effect on SEMA3C expression, making a contribution to dyslexia susceptibility in this family.

Two offshore coral species show greater acclimatization capacity to environmental variation than nearshore counterparts in southern Belize - J. H. Baumann; C. B. Bove; L. Carne; I. Gutierrez; K. D. Castillo (Coral Reefs, 2021)

Exposure duration modulates the response of Caribbean corals to global change stressors - Hannah E. Aichelman; Colleen B. Bove; Karl D. Castillo; Jessica M. Boulton; Alyssa C. Knowlton; Olivia C. Nieves; Justin B. Ries; Sarah W. Davies (Limnology and Oceanography, 2021)
Global change, including rising temperatures and acidification, threatens corals globally. Although bleaching events reveal fine‐scale patterns of resilience, traits enabling persistence under global change remain elusive. We conducted a 95‐d controlled‐laboratory experiment investigating how duration of exposure to warming (~28, 31°C), acidification ( p CO 2 ~ 343 [present day], ~663 [end of century], ~3109 [extreme] μ atm), and their combination influences physiology of reef‐building corals ( Siderastrea siderea , Pseudodiploria strigosa ) from two reef zones on the Belize Mesoamerican Barrier Reef System. Every 30 d, net calcification rate, host protein and carbohydrate, chlorophyll a , and symbiont density were quantified for the same coral individual to characterize acclimation potential under global change. Coral physiologies of the two species were differentially affected by stressors and exposure duration was found to modulate these responses. Siderastrea siderea exhibited resistance to end of century p CO 2 and temperature stress, but calcification was negatively affected by extreme p CO 2 . However, S. siderea calcification rates remained positive after 95 d of extreme p CO 2 conditions, suggesting acclimation. In contrast, P. strigosa was more negatively influenced by elevated temperatures, which reduced most physiological parameters. An exception was nearshore P. strigosa , which maintained calcification rates under elevated temperature, suggesting local adaptation to the warmer environment of their natal reef zone. This work highlights how tracking coral physiology across various exposure durations can capture acclimatory responses to global change stressors.

Assisted phytoremediation of lead contaminated soil using Atriplex halimus and its effect on some soil physical properties - E. Acuña; B. Castillo; M. Queupuan; M. Casanova; Y. Tapia (International Journal of Environmental Science and Technology, 2021)

A Matter of Scale: Population Genomic Structure and Connectivity of Fisheries At-Risk Common Dolphins (Delphinus delphis) From Australasia - Andrea Barceló; Jonathan Sandoval-Castillo; Karen A. Stockin; Kerstin Bilgmann; Catherine R. M. Attard; Nikki Zanardo; Guido J. Parra; Krista Hupman; Isabella M. Reeves; Emma L. Betty; Gabriela Tezanos-Pinto; Luciano B. Beheregaray; et al. (Frontiers in Marine Science, 2021)
An understanding of population structure and connectivity at multiple spatial scales is required to assist wildlife conservation and management. This is particularly critical for widely distributed and highly mobile marine mammals subject to fisheries by-catch. Here, we present a population genomic assessment of a near-top predator, the common dolphin ( Delphinus delphis ), which is incidentally caught in multiple fisheries across the Australasian region. The study was carried out using 14,799 ddRAD sequenced genome-wide markers genotyped for 478 individuals sampled at multiple spatial scales across Australasia. A complex hierarchical metapopulation structure was identified, with three highly distinct and genetically diverse regional populations at large spatial scales (>1,500 km). The populations inhabit the southern coast of Australia, the eastern coast of Australia, New Zealand, and Tasmania, with the latter also showing a considerable level of admixture to Australia's east coast. Each of these regional populations contained two to four nested local populations (i.e., subpopulations) at finer spatial scales, with most of the gene flow occurring within distances of 50 to 400 km. Estimates of contemporary migration rates between adjacent subpopulations ranged from 6 to 25%. Overall, our findings identified complex common dolphin population structure and connectivity across state and international jurisdictions, including migration and gene flow across the Tasman Sea. The results indicate that inter-jurisdictional collaboration is required to implement conservation management strategies and mitigate fisheries interactions of common dolphins across multiple spatial scales in the Australasian region.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Nutritional factors modulating plant and fruit susceptibility to pathogens: BARD workshop, Haifa, Israel, February 25–26, 2018 - Dov Prusky; Leandro José de Assis; Riccardo Baroncelli; Ernesto P. Benito; Virginia Casado del Castillo; Timothy Chaya; Shay Covo; José María Díaz-Mínguez; Nicole M. Donofrio; Eduardo Espeso; Tânia Ribeiro Fernandes; Gustavo H. Goldman; et al. (Phytoparasitica, 2020)

Oceanographic heterogeneity influences an ecological radiation in elasmobranchs - Jonathan Sandoval‐Castillo; Luciano B. Beheregaray (Journal of Biogeography, 2020)
Aim During ecological speciation, reproductive isolation is predicted to evolve between populations adapted to different biotic or abiotic environments despite the absence of geographical isolation. Regions of oceanographic heterogeneity (e.g. current interfaces, habitat transition zones, ecological gradients) are strong candidates for the presence of ecologically divergent natural selection, but their role in the radiation of elasmobranch species is yet to be tested. We used an integrative framework to assess the relative influence of oceanographic heterogeneity and geological history on the diversification of an elasmobranch genus. Location Gulf of California (GC) and Baja California Peninsula (BCP), Mexico. Taxon Shovelnose guitarfish (genus Pseudobatos ). Methods We sampled 210 Pseudobatos specimens from four distinct but physically connected oceanographic regions within the GC and in the BCP. We used genetic (mtDNA sequences and AFLP genotypes) and environmental (six oceanographic variables) datasets to clarify phylogenetic relationships, demographic history and evolutionary divergence among populations, and to test for associations between ecologically driven selection and reproductive isolation. Results Phylogenetic and population genetic evidence exposed five distinct lineages of Pseudobatos in the region, including four cryptic lineages in the GC. Phylogeographic analyses indicate a recent history of ecologically driven diversification associated with the Gulf's young oceanographic environment and its four ecologically discrete regions. This hypothesis was supported by seascape genetics, ecological niche modelling and by tests of selection. Main conclusions We propose an adaptive radiation for the genus Pseudobatos linked with habitat heterogeneity of the GC. Our study likely represents the first assessment of an ecological radiation in the highly diverse elasmobranch group. It capitalizes on the environmental and biogeographic settings of the GC to offer a new perspective about the application of integrative approaches to study divergent natural selection and diversification in the sea.

Could Alternaria solani IA300 be a plant growth-promoting fungus? - Jorge A. Mauricio-Castillo; Silvia Salas-Muñoz; Luis R. Reveles-Torres; Miguel A. Salas-Luevano; Fatima B. Salazar-Badillo (European Journal of Plant Pathology, 2020)

Meta-Analysis Reveals Reduced Coral Calcification Under Projected Ocean Warming but Not Under Acidification Across the Caribbean Sea - Colleen B. Bove; James Umbanhowar; Karl D. Castillo (Frontiers in Marine Science, 2020)

Nitrogen assimilation in picocyanobacteria inhabiting the oxygen‐deficient waters of the eastern tropical North and South Pacific - Montserrat Aldunate; Carlos Henríquez‐Castillo; Qixing Ji; Jessica Lueders‐Dumont; Margaret R. Mulholland; Bess B. Ward; Peter von Dassow; Osvaldo Ulloa (Limnology and Oceanography, 2020)
Prochlorococcus and Synechococcus are the most abundant free‐living photosynthetic microorganisms in the ocean. Uncultivated lineages of these picocyanobacteria also thrive in the dimly illuminated upper part of oxygen‐deficient zones (ODZs), where an important portion of ocean nitrogen (N) loss takes place via denitrification and anaerobic ammonium oxidation. Recent metagenomic studies revealed that ODZ Prochlorococcus have the genetic potential for using different N forms, including nitrate and nitrite, uncommon N sources for Prochlorococcus , but common for Synechococcus . To determine which N sources ODZ picocyanobacteria are actually using in nature, the cellular 15 N natural abundance (δ 15 N) and assimilation rates of different N compounds were determined using cell sorting by flow cytometry and mass spectrometry. The natural δ 15 N of the ODZ Prochlorococcus varied from −4.0‰ to 13.0‰ ( n = 9), with 50% of the values in the range of −2.1–2.6‰. While the highest values suggest nitrate use, most observations indicate the use of nitrite, ammonium, or a mixture of N sources. Meanwhile, incubation experiments revealed potential assimilation rates of ammonium and urea in the same order of magnitude as that expected for total N in several environments including ODZs, whereas rates of nitrite and nitrate assimilation were very low. Our results thus indicate that reduced forms of N and nitrite are the dominant sources for ODZ picocyanobacteria, although nitrate might be important on some occasions. ODZ picocyanobacteria might thus represent potential competitors with anammox bacteria for ammonium and nitrite, with ammonia‐oxidizing archaea for ammonium, and with nitrite‐oxidizing bacteria for nitrite.

Accumulation of Sulphur in Atriplex nummularia Cultivated in Mine Tailings and Effect of Organic Amendments Addition - Y. Tapia; B. Loch; B. Castillo; E. Acuña; M. Casanova; O. Salazar; P. Cornejo; M. Antilén (Water, Air, & Soil Pollution, 2020)

Utilization of naproxen by Amycolatopsis sp. Poz 14 and detection of the enzymes involved in the degradation metabolic pathway - B. M. Alanis-Sánchez; S. M. Pérez-Tapia; S. Vázquez-Leyva; I. Mejía-Calvo; Z. Macías-Palacios; L. Vallejo-Castillo; C. M. Flores-Ortiz; C. Guerrero-Barajas; J. A. Cruz-Maya; J. Jan-Roblero (World Journal of Microbiology and Biotechnology, 2019)

Windbreak Wall-Vegetative Strip System to Reduce Air Emissions from Mechanically Ventilated Livestock Barns—Part 3: Layer House Evaluation - Ali Ajami; Sanjay B. Shah; Lingjuan Wang-Li; Praveen Kolar; Miguel S. Castillo (Water, Air, & Soil Pollution, 2019)

Windbreak Wall-Vegetative Strip System to Reduce Air Emissions from Mechanically Ventilated Livestock Barns: Part 2—Swine House Evaluation - Ali Ajami; Sanjay B. Shah; Lingjuan Wang-Li; Praveen Kolar; Miguel S. Castillo (Water, Air, & Soil Pollution, 2019)

Genetically informed captive breeding of hybrids of an extinct species of Galapagos tortoise - Maud C. Quinzin; Jonathan Sandoval‐Castillo; Joshua M. Miller; Luciano B. Beheregaray; Michael A. Russello; Elizabeth A. Hunter; James P. Gibbs; Washington Tapia; Freddy Villalva; Adalgisa Caccone (Conservation Biology, 2019)
Hybridization poses a major challenge for species conservation because it threatens both genetic integrity and adaptive potential. Yet, hybridization can occasionally offer unprecedented opportunity for species recovery if the genome of an extinct taxon is present among living hybrids such that selective breeding could recapture it. We explored the design elements for establishing a captive‐breeding program for Galapagos tortoises ( Chelonoidis spp.) built around individuals with admixed ancestry involving an extinct species. The target individuals were hybrids between the extinct species from Floreana Island, C. niger , and an extant species, C. becki , which were recently found in the endemic range of C. becki , from Wolf Volcano on Isabela Island. We combined genotypic data from 35 tortoises with high ancestry from C. niger with forward‐in‐time simulations to explore captive breeding strategies that maximized overall genetic diversity and ancestry from C. niger while accommodating resource constraints, species biology, and the urgency to return tortoises to Floreana Island for facilitating ecosystem restoration. Overall genetic diversity was maximized when in the simulation tortoises were organized in relatively small breeding groups. Substantial amounts of the C. niger genome were captured despite limited resources available for selectively breeding tortoises in captivity. Genetic diversity was maximized when captive‐bred offspring were released to the wild rather than being used as additional breeders. Our results provide genetic‐based and practical guidance on the inclusion of hybrids with genomic representation from extinct taxa into species restoration programs and informs the ongoing debate on the value of hybrids in biodiversity conservation.

Availability of copper in mine tailings with humic substance addition and uptake by Atriplex halimus - Y. Tapia; M. Casanova; B. Castillo; E. Acuña; J. Covarrubias; M. Antilén; A. Masaguer (Environmental Monitoring and Assessment, 2019)

Nearshore coral growth declining on the Mesoamerican Barrier Reef System - Justin H. Baumann; Justin B. Ries; John P. Rippe; Travis A. Courtney; Hannah E. Aichelman; Isaac Westfield; Karl D. Castillo (Global Change Biology, 2019)
Anthropogenic global change and local stressors are impacting coral growth and survival worldwide, altering the structure and function of coral reef ecosystems. Here, we show that skeletal extension rates of nearshore colonies of two abundant and widespread Caribbean corals ( Siderastrea siderea , Pseudodiploria strigosa ) declined across the Belize Mesoamerican Barrier Reef System (MBRS) over the past century, while offshore coral conspecifics exhibited relatively stable extension rates over the same temporal interval. This decline has caused nearshore coral extension rates to converge with those of their historically slower growing offshore coral counterparts. For both species, individual mass coral bleaching events were correlated with low rates of skeletal extension within specific reef environments, but no single bleaching event was correlated with low skeletal extension rates across all reef environments. We postulate that the decline in skeletal extension rates for nearshore corals is driven primarily by the combined effects of long‐term ocean warming and increasing exposure to higher levels of land‐based anthropogenic stressors, with acute thermally induced bleaching events playing a lesser role. If these declining trends in skeletal growth of nearshore S. siderea and P. strigosa continue into the future, the structure and function of these critical nearshore MBRS coral reef systems is likely to be severely impaired.

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Effects of Recreational Soccer on Health Outcomes: A Narrative Review - Israel Castillo-Bellot; Jose Mora-Gonzalez; Luis Fradua; Francisco B. Ortega; Luis Gracia-Marco (Journal of Science in Sport and Exercise, 2019)

Diffuse Hydrothermal Venting: A Hidden Source of Iron to the Oceans - Alastair J. M. Lough; Douglas P. Connelly; William B. Homoky; Jeffrey A. Hawkes; Valerie Chavagnac; Alain Castillo; Majid Kazemian; Ko-ichi Nakamura; Tohru Araki; Burkhard Kaulich; Rachel A. Mills (Frontiers in Marine Science, 2019)

A relapsing fever Borrelia and spotted fever Rickettsia in ticks from an Andean valley, central Chile - Sebastián Muñoz-Leal; Arlei Marcili; Danny Fuentes-Castillo; Mauricio Ayala; Marcelo B. Labruna (Experimental and Applied Acarology, 2019)

A High-Demanding Strategy to Ensure the Highest Quality Standards of Oral Liquid Individualized Medicines for Pediatric Use - Javier Suárez-González; Ana Santoveña-Estévez; Sofía Armijo-Ruíz; Aurora Castillo; José B. Fariña (AAPS PharmSciTech, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Antiretroviral Hydrophobic Core Graft-Copolymer Nanoparticles: The Effectiveness against Mutant HIV-1 Strains and in Vivo Distribution after Topical Application - Anita Leporati; Suresh Gupta; Elijah Bolotin; Gerardo Castillo; Joshua Alfaro; Marina B. Gottikh; Alexei A. Bogdanov Jr (Pharmaceutical Research, 2019)

Metal and metalloid immobilization by microbiologically induced carbonates precipitation - Diana P. Tamayo-Figueroa; Elianna Castillo; Pedro F. B. Brandão (World Journal of Microbiology and Biotechnology, 2019)

Chilling and forcing temperatures interact to predict the onset of wood formation in Northern Hemisphere conifers - Nicolas Delpierre; Ségolène Lireux; Florian Hartig; Jesus Julio Camarero; Alissar Cheaib; Katarina Čufar; Henri Cuny; Annie Deslauriers; Patrick Fonti; Jožica Gričar; Jian‐Guo Huang; Cornelia Krause; et al. (Global Change Biology, 2019)
The phenology of wood formation is a critical process to consider for predicting how trees from the temperate and boreal zones may react to climate change. Compared to leaf phenology, however, the determinism of wood phenology is still poorly known. Here, we compared for the first time three alternative ecophysiological model classes ( threshold models, heat‐sum models and chilling‐influenced heat‐sum models) and an empirical model in their ability to predict the starting date of xylem cell enlargement in spring, for four major Northern Hemisphere conifers ( Larix decidua, Pinus sylvestris , Picea abies and Picea mariana ). We fitted models with Bayesian inference to wood phenological data collected for 220 site‐years over Europe and Canada. The chilling‐influenced heat‐sum model received most support for all the four studied species, predicting validation data with a 7.7‐day error, which is within one day of the observed data resolution. We conclude that both chilling and forcing temperatures determine the onset of wood formation in Northern Hemisphere conifers. Importantly, the chilling‐influenced heat‐sum model showed virtually no spatial bias whichever the species, despite the large environmental gradients considered. This suggests that the spring onset of wood formation is far less affected by local adaptation than by environmentally driven plasticity. In a context of climate change, we therefore expect rising winter–spring temperature to exert ambivalent effects on the spring onset of wood formation, tending to hasten it through the accumulation of forcing temperature, but imposing a higher forcing temperature requirement through the lower accumulation of chilling.

Apparent timing of density banding in the Caribbean coral Siderastrea siderea suggests complex role of key physiological variables - B. E. Benson; J. P. Rippe; C. B. Bove; K. D. Castillo (Coral Reefs, 2019)

Realized niche and spatial pattern of native and exotic halophyte hybrids - B. Gallego-Tévar; G. Curado; B. J. Grewell; M. E. Figueroa; J. M. Castillo (Oecologia, 2018)

Corals sustain growth but not skeletal density across the Florida Keys Reef Tract despite ongoing warming - John P. Rippe; Justin H. Baumann; Daphne N. De Leener; Hannah E. Aichelman; Eric B. Friedlander; Sarah W. Davies; Karl D. Castillo (Global Change Biology, 2018)
Through the continuous growth of their carbonate skeletons, corals record information about past environmental conditions and their effect on colony fitness. Here, we characterize century‐scale growth records of inner and outer reef corals across ~200 km of the Florida Keys Reef Tract (FKRT) using skeletal cores extracted from two ubiquitous reef‐building species, Siderastrea siderea and Pseudodiploria strigosa . We find that corals across the FKRT have sustained extension and calcification rates over the past century but have experienced a long‐term reduction in skeletal density, regardless of reef zone. Notably, P. strigosa colonies exhibit temporary reef zone‐dependent reductions in extension rate corresponding to two known extreme temperature events in 1969–1970 and 1997–1998. We propose that the subtropical climate of the FKRT may buffer corals from chronic growth declines associated with climate warming, though the significant reduction in skeletal density may indicate underlying vulnerability to present and future trends in ocean acidification.

Symbiodinium Functional Diversity in the Coral Siderastrea siderea Is Influenced by Thermal Stress and Reef Environment, but Not Ocean Acidification - Sarah W. Davies; Justin B. Ries; Adrian Marchetti; Karl D. Castillo (Frontiers in Marine Science, 2018)

Seascape genomics reveals adaptive divergence in a connected and commercially important mollusc, the greenlip abalone ( Haliotis laevigata ), along a longitudinal environmental gradient - Jonathan Sandoval‐Castillo; Nick A. Robinson; Anthony M. Hart; Lachlan W. S. Strain; Luciano B. Beheregaray (Molecular Ecology, 2018)
Populations of broadcast spawning marine organisms often have large sizes and are exposed to reduced genetic drift. Under such scenarios, strong selection associated with spatial environmental heterogeneity is expected to drive localized adaptive divergence, even in the face of connectivity. We tested this hypothesis using a seascape genomics approach in the commercially important greenlip abalone ( Haliotis laevigata ). We assessed how its population structure has been influenced by environmental heterogeneity along a zonal coastal boundary in southern Australia linked by strong oceanographic connectivity. Our data sets include 9,109 filtered SNP s for 371 abalones from 13 localities and environmental mapping across ~800 km. Genotype–environment association analyses and outlier tests defined 8,786 putatively neutral and 323 candidate adaptive loci. From a neutral perspective, the species is better represented by a metapopulation with very low differentiation (global F ST = 0.0081) and weak isolation by distance following a stepping‐stone model. For the candidate adaptive loci, however, model‐based and model‐free approaches indicated five divergent population clusters. After controlling for spatial distance, the distribution of putatively adaptive variation was strongly correlated to selection linked to minimum sea surface temperature and oxygen concentration. Around 80 candidates were annotated to genes with functions related to high temperature and/or low oxygen tolerance, including genes that influence the resilience of abalone species found in other biogeographic regions. Our study includes a documented example about the uptake of genomic information in fisheries management and supports the hypothesis of adaptive divergence due to coastal environmental heterogeneity in a connected metapopulation of a broadcast spawner.

Ecological disturbance influences adaptive divergence despite high gene flow in golden perch ( Macquaria ambigua ): Implications for management and resilience to climate change - Catherine R. M. Attard; Chris J. Brauer; Jonathan Sandoval‐Castillo; Leanne K. Faulks; Peter J. Unmack; Dean M. Gilligan; Luciano B. Beheregaray (Molecular Ecology, 2018)
Populations that are adaptively divergent but maintain high gene flow may have greater resilience to environmental change as gene flow allows the spread of alleles that have already been tested elsewhere. In addition, populations naturally subjected to ecological disturbance may already hold resilience to future environmental change. Confirming this necessitates ecological genomic studies of high dispersal, generalist species. Here we perform one such study on golden perch ( Macquaria ambigua ) in the Murray‐Darling Basin ( MDB ), Australia, using a genome‐wide SNP data set. The MDB spans across arid to wet and temperate to subtropical environments, with low to high ecological disturbance in the form of low to high hydrological variability. We found high gene flow across the basin and three populations with low neutral differentiation. Genotype–environment association analyses detected adaptive divergence predominantly linked to an arid region with highly variable riverine flow, and candidate loci included functions related to fat storage, stress and molecular or tissue repair. The high connectivity of golden perch in the MDB will likely allow locally adaptive traits in its most arid and hydrologically variable environment to spread and be selected in localities that are predicted to become arid and hydrologically variable in future climates. High connectivity in golden perch is likely due to their generalist life history and efforts of fisheries management. Our study adds to growing evidence of adaptation in the face of gene flow and highlights the importance of considering ecological disturbance and adaptive divergence in biodiversity management.

Impact of severe hematological abnormalities in the outcome of hospitalized patients with influenza virus infection - A. Lalueza; H. Trujillo; J. Laureiro; B. Ayuso; P. Hernández-Jiménez; C. Castillo; M. Torres; D. Folgueira; O. Madrid; C. Díaz-Pedroche; E. Arrieta; C. Arévalo; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Predicting monthly precipitation along coastal Ecuador: ENSO and transfer function models - Lelys B. de Guenni; Mariangel García; Ángel G. Muñoz; José L. Santos; Alexandra Cedeño; Carlos Perugachi; José Castillo (Theoretical and Applied Climatology, 2017)

Estimation of natural outcrossing rate and genetic diversity in Lima bean (Phaseolus lunatus L. var. lunatus) from Brazil using SSR markers: implications for conservation and breeding - J. S. Penha; A. C. A. Lopes; R. L. F. Gomes; J. B. Pinheiro; J. R. Assunção Filho; E. A. Silvestre; J. P. G. Viana; J. Martínez-Castillo (Genetic Resources and Crop Evolution, 2017)

A simulation tool for advanced design and management of collective sprinkler-irrigated areas: a study case - N. Zapata; E. H. El Malki; B. Latorre; J. Gallinat; F. J. Citoler; R. Castillo; E. Playán (Irrigation Science, 2017)

Ideal cardiovascular health and liver enzyme levels in European adolescents; the HELENA study - Idoia Labayen; Jonatan R. Ruiz; Inge Huybrechts; Francisco B. Ortega; Manuel Castillo; Michael Sjöstrom; Marcela González-Gross; Yannis Manios; Kurt Widhalm; Anthony Kafatos; Christina Breidenassel; Gerardo Rodríguez; et al. (Journal of Physiology and Biochemistry, 2017)

Effects of cryopreservation on mitochondria of fish spermatozoa - Elías Figueroa; Iván Valdebenito; Andrea B. Zepeda; Carolina A. Figueroa; Kelly Dumorné; Rodrigo L. Castillo; Jorge G. Farias (Reviews in Aquaculture, 2017)
The development of sperm cryopreservation has enabled transcendental changes to occur in the reproductive biotechnology of both mammals and fish; it has become a basic tool for animal improvement. Nevertheless, these protocols cause damage to cell structure and physiology, altering sperm functioning due to cryo‐injuries during freezing and thawing. However, studies of the effects on the structural, functional and genomic stability of the mitochondria in fish spermatozoa during cryopreservation are still lacking. The object of this review was to analyse the effect of cryopreservation on mitochondrial metabolic pathways in fish spermatozoa. This effect is related with the bioenergy mechanism for flagellar movement during the activation of sperm motility. In teleost fish, the mitochondria may be cylindrical, spherical or irregular in shape and adhere in a helicoidal or conical pattern to the middle piece. The salmonidae have only a single mitochondrion, but this may vary in other species; the mitochondria provide the flagellum with energy during sperm motility, when sperm respiration is essential. The effects of cryopreservation can induce structural damage to the mitochondria, altering the biochemical process involved in ATP production and thus causing a reduction in sperm motility. Fragmentation damage to nuclear DNA and diminution in sperm motility is mainly associated with damage to the structure and metabolic functioning of the mitochondrion. A direct correlation exists between the mitochondrial membrane potential (transmembrane integrity, ∆ Ψ m ) and the motility and fertilizing capacity of the cryopreserved spermatozoa, confirming that this organelle is the energy nucleus of the spermatozoon and that the cessation or prolongation of motility and successful fertilization depend on the availability of ATP in the spermatozoa. Further works are need to incorporate biotechnology studies, at cell and molecular level, of the possible effects of cryopreservation on mitochondrial DNA , enzymatic or metabolic modifications of the citric acid cycle, and the oxidative phosphorylation process in the inner membrane, as well as studies of the mitochondrial ultrastructure. Thus, mitochondrial dynamics could be established as a potential target for therapeutic strategies.

Tannins and mimosine in Leucaena genotypes and their relations to Leucaena resistance against Leucaena Psyllid and Onion thrips - Ahmed M. M. Ahmed; Francisco J. Solorio Sánchez; Luis Ramírez y Avilés; Rasha Ezzat Elsaid Mahdy; J. B. Castillo Camaal (Agroforestry Systems, 2017)

An overview of Australia's temperate marine phylogeography, with new evidence from high‐dispersal gastropods - Peter R. Teske; Jonathan Sandoval‐Castillo; Jonathan Waters; Luciano B. Beheregaray (Journal of Biogeography, 2017)
Aim We provide an overview of the location and ages of coastal phylogeographical breaks in southern Australian planktonic dispersers, and test the hypothesis that the absence of such breaks in some species is an artefact of insufficient resolution of genetic markers when such breaks evolved comparatively recently. Location Temperate coastal Australia. Methods We generated a large (> 1500 individuals) data set from rapidly evolving microsatellite markers for two codistributed Australian coastal gastropods, and compared it with mitochondrial DNA data. Both study species, the snail Nerita atramentosa and the limpet Siphonaria diemenensis , have long planktonic dispersal phases, and neither taxon exhibits substantial regional genetic structure on the basis of mitochondrial DNA . We tested for the presence of genetic structure by means of AMOVA , Bayesian clustering ( structure ) and iterated realloction ( flock ). Results There was no compelling evidence for the existence of more than one evolutionary lineage in either species. Main conclusions Discrepancies in the phylogeographical structuring of co‐distributed intertidal taxa cannot be attributed to insufficient marker resolution for the two species considered here, and likely reflect a combination of abiotic and biotic factors that include porous dispersal barriers, life history and species age/history. It appears that contemporary oceanography does not explain the presence of phylogeographical breaks, but may serve to maintain breaks that evolved earlier. Deep genetic divergence in some of the previously studied coastal invertebrates suggests that these could be cryptic species, in which case competitive exclusion may play a role in constraining species biogeography.

Spartina versicolor Fabre: Another case of Spartina trans-Atlantic introduction? - A. Baumel; M. Rousseau-Gueutin; C. Sapienza-Bianchi; A. Gareil; N. Duong; H. Rousseau; O. Coriton; R. Amirouche; S. Sciandrello; B. Duarte; I. Caçador; J. M. Castillo; et al. (Biological Invasions, 2016)

Thermal and pCO2 Stress Elicit Divergent Transcriptomic Responses in a Resilient Coral - Sarah W. Davies; Adrian Marchetti; Justin B. Ries; Karl D. Castillo (Frontiers in Marine Science, 2016)

Drivers of fluorescent dissolved organic matter in the global epipelagic ocean - T. S. Catalá; X. A. Álvarez‐Salgado; J. Otero; F. Iuculano; B. Companys; B. Horstkotte; C. Romera‐Castillo; M. Nieto‐Cid; M. Latasa; X. A. G. Morán; J. M. Gasol; C. Marrasé; et al. (Limnology and Oceanography, 2016)
Fluorescent dissolved organic matter (FDOM) in open surface waters ( 70%) than for the amino acid‐like components ( a . Positive non‐linear relationships between both predictor variables and the two humic‐like PARAFAC components suggest that their distribution are biologically controlled. Compared with the dark ocean (> 200 m), the relationships of C1 and C2 with AOU indicate a higher C1/AOU and C2/AOU ratios of the humic‐like substances in the dark ocean than in the surface ocean where a net effect of photobleaching is also detected. C3 (tryptophan‐like) and C4 (tyrosine‐like) variability was mostly dictated by salinity ( S ), by means of positive non‐linear relationships, suggesting a primary physical control of their distributions at the global surface ocean scale that could be related to the changing evaporation‐precipitation regime. Remarkably, bacterial biomass (BB) only contributed to explain a minor part of the variability of C1 and C4.

Habitat availability and gene flow influence diverging local population trajectories under scenarios of climate change: a place‐based approach - Donelle Schwalm; Clinton W. Epps; Thomas J. Rodhouse; William B. Monahan; Jessica A. Castillo; Chris Ray; Mackenzie R. Jeffress (Global Change Biology, 2016)
Ecological niche theory holds that species distributions are shaped by a large and complex suite of interacting factors. Species distribution models ( SDM s) are increasingly used to describe species’ niches and predict the effects of future environmental change, including climate change. Currently, SDM s often fail to capture the complexity of species’ niches, resulting in predictions that are generally limited to climate‐occupancy interactions. Here, we explore the potential impact of climate change on the American pika using a replicated place‐based approach that incorporates climate, gene flow, habitat configuration, and microhabitat complexity into SDM s. Using contemporary presence–absence data from occupancy surveys, genetic data to infer connectivity between habitat patches, and 21 environmental niche variables, we built separate SDM s for pika populations inhabiting eight US National Park Service units representing the habitat and climatic breadth of the species across the western United States. We then predicted occurrence probability under current (1981–2010) and three future time periods (out to 2100). Occurrence probabilities and the relative importance of predictor variables varied widely among study areas, revealing important local‐scale differences in the realized niche of the American pika. This variation resulted in diverse and – in some cases – highly divergent future potential occupancy patterns for pikas, ranging from complete extirpation in some study areas to stable occupancy patterns in others. Habitat composition and connectivity, which are rarely incorporated in SDM projections, were influential in predicting pika occupancy in all study areas and frequently outranked climate variables. Our findings illustrate the importance of a place‐based approach to species distribution modeling that includes fine‐scale factors when assessing current and future climate impacts on species’ distributions, especially when predictions are intended to manage and conserve species of concern within individual protected areas.

Closing the gaps on the viral photosystem‐ I psa DCAB gene organization - Sheila Roitman; José Flores‐Uribe; Alon Philosof; Ben Knowles; Forest Rohwer; J. Cesar Ignacio‐Espinoza; Matthew B. Sullivan; Francisco M. Cornejo‐Castillo; Pablo Sánchez; Silvia G. Acinas; Chris L. Dupont; Oded Béjà (Environmental Microbiology, 2015)
Summary Marine photosynthesis is largely driven by cyanobacteria, namely S ynechococcus and P rochlorococcus . Genes encoding for photosystem ( PS ) I and II reaction centre proteins are found in cyanophages and are believed to increase their fitness. Two viral PSI gene arrangements are known, psaJF→ C →A→ B → K → E → D and psaD→ C →A→ B . The shared genes between these gene cassettes and their encoded proteins are distinguished by %G + C and protein sequence respectively. The data on the psaD→ C →A→ B gene organization were reported from only two partial gene cassettes coming from Global Ocean Sampling stations in the P acific and I ndian oceans. Now we have extended our search to 370 marine stations from six metagenomic projects. Genes corresponding to both PSI gene arrangements were detected in the P acific, I ndian and A tlantic oceans, confined to a strip along the equator (30°N and 30°S). In addition, we found that the predicted structure of the viral PsaA protein from the psaD→ C → A → B organization contains a lumenal loop conserved in PsaA proteins from S ynechococcus , but is completely absent in viral PsaA proteins from the psaJF→ C → A → B → K → E → D gene organization and most P rochlorococcus strains. This may indicate a co‐evolutionary scenario where cyanophages containing either of these gene organizations infect cyanobacterial ecotypes biogeographically restricted to the 30°N and 30°S equatorial strip.

A Study on the Knowledge, Perception, and Use of Breast Cancer Screening Methods and Quality of Care Among Women from Central Mexico - Andrea B. Cruz-Castillo; María A. Hernández-Valero; Shelly R. Hovick; Martha Elva Campuzano-González; Miguel Angel Karam-Calderón; L. Patricia Bustamante-Montes (Journal of Cancer Education, 2015)

Application of Focused Ultrasound-Assisted Extraction to the Determination of Persistent Organic Pollutants (POPs) in Soil Samples - R. Flores-Ramírez; S. E. Medellín-Garibay; C. G. Castillo; C. A. Ilizaliturri-Hernández; B. A. Zuki-Orozco; L. Batres-Esquivel; F. Díaz-Barriga (Bulletin of Environmental Contamination and Toxicology, 2015)

Management of Perennial Warm-Season Bioenergy Grasses. II. Seasonal Differences in Elephantgrass and Energycane Morphological Characteristics Affect Responses to Harvest Frequency and Timing - Chae-In Na; Lynn E. Sollenberger; John E. Erickson; Kenneth R. Woodard; Miguel S. Castillo; M. Kimberly Mullenix; João M. B. Vendramini; Maria L. Silveira (BioEnergy Research, 2015)

Invasive Populations of Elephantgrass Differ in Morphological and Growth Characteristics from Clones Selected for Biomass Production - Lynn E. Sollenberger; Kenneth R. Woodard; João M. B. Vendramini; John E. Erickson; Kenneth A. Langeland; M. Kimberly Mullenix; Chaein Na; Miguel S. Castillo; Maria Gallo; Christine D. Chase; Yolanda López (BioEnergy Research, 2014)

Biodiversity and indigenous management of the endangered non-toxic germplasm of Jatropha curcas L. in the Totonacapan (Mexico), and the implications for its conservation - Yolanda B. Vera-Castillo; Jesús A. Cuevas; Ana G. Valenzuela-Zapata; Beatriz Urbano; Fernando González-Andrés (Genetic Resources and Crop Evolution, 2014)

Prospecting metal-resistant plant-growth promoting rhizobacteria for rhizoremediation of metal contaminated estuaries using Spartina densiflora - L. Andrades-Moreno; I. del Castillo; R. Parra; B. Doukkali; S. Redondo-Gómez; P. Pérez-Palacios; M. A. Caviedes; E. Pajuelo; I. D. Rodríguez-Llorente (Environmental Science and Pollution Research, 2014)

Low dispersive modeling of Rayleigh waves on partly staggered grids - O. Rojas; B. Otero; J. E. Castillo; S. M. Day (Computational Geosciences, 2014)

Huddling up in a dry environment: the physiological benefits of aggregation in an intertidal gastropod - José M. Rojas; Simón B. Castillo; Joan B. Escobar; Jennifer L. Shinen; Francisco Bozinovic (Marine Biology, 2013)

Rapid isolation of 14 microsatellite markers for Van Diemen’s siphon limpet Siphonaria diemenensis - Jonathan Sandoval-Castillo; Michael G. Gardner; Luciano B. Beheregaray (Conservation Genetics Resources, 2012)

Isolation and characterization of microsatellite markers for the marine black nerite Nerita atramentosa: tools for assessment and design of marine protected areas - Jonathan Sandoval-Castillo; Michael G. Gardner; Luciano B. Beheregaray (Conservation Genetics Resources, 2012)

A new strain of tomato severe leaf curl virus and a unique variant of tomato yellow leaf curl virus from Mexico - B. Bañuelos-Hernández; J. A. Mauricio-Castillo; Y. Cardenas-Conejo; R. G. Guevara-González; G. R. Arguello-Astorga (Archives of Virology, 2012)

Evaluation of an immunochromatographic dip strip test for simultaneous detection of Cryptosporidium spp, Giardia duodenalis, and Entamoeba histolytica antigens in human faecal samples - P. Goñi; B. Martín; M. Villacampa; A. García; C. Seral; F. J. Castillo; A. Clavel (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Muscular strength and markers of insulin resistance in European adolescents: the HELENA Study - D. Jiménez-Pavón; F. B. Ortega; J. Valtueña; J. Castro-Piñero; S. Gómez-Martínez; M. Zaccaria; F. Gottrand; D. Molnár; M. Sjöström; M. González-Gross; M. J. Castillo; L. A. Moreno; et al. (European Journal of Applied Physiology, 2012)

Chemotypical variation in Vanilla planifolia Jack. (Orchidaceae) from the Puebla-Veracruz Totonacapan region - Víctor Manuel Salazar-Rojas; B. Edgar Herrera-Cabrera; Adriana Delgado-Alvarado; Marcos Soto-Hernández; Fernando Castillo-González; Mario Cobos-Peralta (Genetic Resources and Crop Evolution, 2012)

Potentially pathogenic nontuberculous mycobacteria found in aquatic systems. Analysis from a reclaimed water and water distribution system in Mexico City - A. I. Castillo-Rodal; M. Mazari-Hiriart; L. T. Lloret-Sánchez; B. Sachman-Ruiz; P. Vinuesa; Y. López-Vidal (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Bicarbonate ingestion has no ergogenic effect on consecutive all out sprint tests in BMX elite cyclists - Mikel Zabala; Ana B. Peinado; Francisco J. Calderón; Javier Sampedro; Manuel J. Castillo; Pedro J. Benito (European Journal of Applied Physiology, 2011)

Prevalence, polyphasic identification, and molecular phylogeny of dagger and needle nematodes infesting vineyards in southern Spain - Carlos Gutiérrez-Gutiérrez; Juan E. Palomares Rius; Carolina Cantalapiedra-Navarrete; Blanca B. Landa; Pablo Castillo (European Journal of Plant Pathology, 2011)

Sleep patterns in Spanish adolescents: associations with TV watching and leisure-time physical activity - Francisco B. Ortega; Palma Chillón; Jonatan R. Ruiz; Manuel Delgado; Ulrike Albers; Jesús L. Álvarez-Granda; Ascensión Marcos; Luis A. Moreno; Manuel J. Castillo (European Journal of Applied Physiology, 2010)

Association of physical activity with muscular strength and fat-free mass in adolescents: the HELENA study - Diego Moliner-Urdiales; Francisco B. Ortega; Germán Vicente-Rodriguez; Juan P. Rey-Lopez; Luis Gracia-Marco; Kurt Widhalm; Michael Sjöström; Luis A. Moreno; Manuel J. Castillo; Jonatan R. Ruiz (European Journal of Applied Physiology, 2010)

Morphological variation in Laelia anceps subsp. dawsonii f. chilapensis Soto-Arenas Orchidaceae in traditional home gardens of Chilapa, Guerrero, Mexico - Víctor Manuel Salazar-Rojas; B. Edgar Herrera-Cabrera; Miguel Ángel Soto-Arenas; Fernando Castillo-González (Genetic Resources and Crop Evolution, 2010)

Climbing time to exhaustion is a determinant of climbing performance in high-level sport climbers - Vanesa España-Romero; Francisco B. Ortega Porcel; Enrique G. Artero; David Jiménez-Pavón; Ángel Gutiérrez Sainz; Manuel J. Castillo Garzón; Jonatan R. Ruiz (European Journal of Applied Physiology, 2009)

Interindividual interactions of Molina’s hog-nosed skunksConepatus chinga in the Pampas grassland of Argentina - Juan I. Reppucci; Diego F. Castillo; Mauro Lucherini; Estela M. Luengos Vidal; Emma B. Casanave (Mammal Research, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Carbon emissions from land-use change: an analysis of causal factors in Chiapas, Mexico - M. A. Castillo-Santiago; A. Hellier; R. Tipper; B. H. J. de Jong (Mitigation and Adaptation Strategies for Global Change, 2007)

Identification of Pratylenchus thornei, the cereal and legume root-lesion nematode, based on SCAR-PCR and satellite DNA - S. Carrasco-Ballesteros; P. Castillo; B. J. Adams; E. Pérez-Artés (European Journal of Plant Pathology, 2007)

Influence of Fe concentration in the medium on multicellular pollen grains and haploid plants induced by mannitol pretreatment in barley (Hordeum vulgare L.) - A. Pulido; F. Bakos; A. Castillo; M. P. Vallés; B. Barnabás; A. Olmedilla (Protoplasma, 2006)

Production of doubled haploids in durum wheat (Triticum turgidum L.) through isolated microspore culture - L. Cistué; M. Soriano; A. M. Castillo; M. P. Vallés; J. M. Sanz; B. Echávarri (Plant Cell Reports, 2006)

Influence of thermal history on the response of Montastraea annularis to short-term temperature exposure - K. D. Castillo; B. S. T. Helmuth (Marine Biology, 2005)

Application of the ‘Climafor’ Approach to Estimate Baseline Carbon Emissions of a Forest Conservation Project in the Selva Lacandona, Chiapas, Mexico - B. H. J. De Jong; A. Hellier; M. A. Castillo-Santiago; R. Tipper (Mitigation and Adaptation Strategies for Global Change, 2005)

Growing more rice with less water: Research findings from a study in China - Randoph Barker; To Phuc Tuong; Yuanhua Li; E. G. Castillo; B. A. M. Bouman (Paddy and Water Environment, 2004)

The contribution of ancestry, chance, and past and ongoing selection to adaptive evolution - Amitabh Joshi; Robinson B. Castillo; Laurence D. Mueller (Journal of Genetics, 2003)

Effect of Testosterone Suppression on the Pharmacokinetics of a Potent GnRH Receptor Antagonist - Eugenia A. Iatsimirskaia; Margaret L. Gregory; Kenna L. Anderes; Rosemary Castillo; K. Eric Milgram; David R. Luthin; Ved P. Pathak; Lance C. Christie; Haresh Vazir; Mark B. Anderson; John M. May (Pharmaceutical Research, 2002)

Genetic loci associated with field resistance to late blight in offspring of Solanum phureja and S.tuberosum grown under short-day conditions - M. Ghislain; B. Trognitz; Ma. del R. Herrera; J. Solis; G. Casallo; C. Vásquez; O. Hurtado; R. Castillo; L. Portal; M. Orrillo (Theoretical and Applied Genetics, 2001)

Astrovirus Infection Among Children with Gastroenteritis in the City of Zaragoza, Spain - L. López; F. J. Castillo; M. A. Fernández; A. Clavel; M. C. Rubio; R. Gómez-Lus; B. Cutillas (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Surface-sediment and epilithic diatom pH calibration sets for remote European mountain lakes (AL:PE Project) and their comparison with the Surface Waters Acidification Programme (SWAP) calibration set - N. G. Cameron; H. J. B. Birks; V. J. Jones; F. Berges; J. Catalan; R. J. Flower; J. Garcia; B. Kawecka; K. A. Koinig; A. Marchetto; P. Sánchez-Castillo; R. Schmidt; et al. (Journal of Paleolimnology, 1999)

Desiccated doubled-haploid embryos obtained from microspore culture of barley cv. Igri - A. B. Ryan; A. M. Castillo; M. P. Vallés; J. M. Sanz; L. Cistué (Plant Cell Reports, 1999)

Somatic embryogenesis and plant regeneration from barley cultivars grown in Spain - A. M. Castillo; B. Egaña; J. M. Sanz; L. Cistué (Plant Cell Reports, 1998)

Plant regeneration from encapsulated somatic embryos of Carica papaya L. - B. Castillo; M. A. L. Smith; U. L. Yadava (Plant Cell Reports, 1998)

Environmental preferences of yellowfin tuna ( Thunnus albacares ) at the northern extent of its range - B. A. Block; J. E. Keen; B. Castillo; H. Dewar; E. V. Freund; D. J. Marcinek; R. W. Brill; C. Farwell (Marine Biology, 1997)

Direct somatic embryogenesis from Begonia gracilis explants - B. Castillo; M. A. L. Smith (Plant Cell Reports, 1997)

Direct somatic embryogenesis fromBegonia gracilis explants - B. Castillo; M. A. L. Smith (Plant Cell Reports, 1997)